Dietary intake and health risk characterization of cadmium, lead, and mercury in milkfish (Chanos chanos) and tilapia (Oreochromis spp.) from aquaculture farms surrounding Manila bay, Philippines - Kathlene Cleah D. Benitez; Allysa Ross N. Almagro; Patrick David M. Torres; Karl Bryan S. Perelonia; Bryan E. Tanyag; Jerick Jann M. Quiambao; Ulysses M. Montojo (Regulatory Toxicology and Pharmacology, 2026)

Seasonal patterns and drivers of nitrogen fixation in soybeans - Luiz Felipe Almeida; Federico Gomez; Francisco Palmero; Gabriel Hintz; Adrian Correndo; Jeremy Ross; Mark Licht; Shaun Casteel; Manninder Singh; Seth Naeve; Rachel Vann; Jose Bais; et al. (European Journal of Agronomy, 2026)

Middle Miocene intensification of the deep western boundary current offshore eastern Greenland - Margaret A. Morris; Ross E. Parnell-Turner; Katharina Hochmuth; David D. McNamara; Anne Briais; Leah LeVay; Anita Di Chiara; Tom Dunkley Jones; Boris Th. Karatsolis; Paul N. Pearson; Matthias Sinnesael (Earth and Planetary Science Letters, 2026)

Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

Pagophilic rather than sea ice obligate: effects of sea ice and colony size on Adélie penguin molt location - David G. Ainley; Virginia Morandini; Grant Ballard; William Fraser; Peter Convey; Dean Anderson; Ronald Ross (Frontiers in Marine Science, 2026)
Strongly pagophilic, the Adélie penguin Pygoscelis adeliae has long been designated a sea ice obligate species, which included the requirement to find pack ice on which to molt. However, observations have accumulated over the years to question this attribute; therefore, we investigated this aspect of the species’ natural history strategy through a synthesis of published, unpublished, and historical records obtained Antarctic-wide and with 12 years of time-lapse camera observations at Cape Royds (Ross Island, Antarctica). We describe patterns of molt habitat use at Cape Royds and evaluate whether interannual variation in regional sea ice conditions (which include at Cape Royds both fast ice and pack ice) during the month immediately preceding the molt season (January) is associated with the number of penguins observed molting at the colony (February). At Cape Royds, automatic camera data, 2008–2024, showed interannual variability in both the timing and number of molting penguins. Peak numbers in view of the camera ranged from 75 to 590 individuals (7%–30% of the breeding population); timing of the peak ranged from February 23 to March 2, although the date of the last molting penguin was consistent among years (March 16 and 17). Based on the results from a negative binomial generalized linear model, peak on-land molt counts varied negatively with mean January sea ice concentration (SIC) within the colony’s foraging area and with breeding population size (breeding pairs; more breeders, fewer molters). Though a longer time series might supply more definitive indications, there was a ~2.2% decrease in the number of penguins molting per 1% increase in SIC. Supplying context to Cape Royds patterns, a review of the literature revealed marked geographic heterogeneity in molt habitat, affected by whether sea ice is present during the molt season (February–March), colony size, and access to prey: in some colonies, most individuals return to molt on land (including landfast ice) or coastal glaciers, while at others only a fraction do so, and at several large colonies molt appears to occur primarily in distant pack ice. Earlier qualitative interpretations in the literature suggested that greater SIC promotes on-land molting, but at Cape Royds higher January SIC brought fewer molting penguins. Together with the broader circumpolar evidence, these findings suggest that Adélie penguin molt habitat is more context-dependent and variable than implied by a simple obligate sea ice paradigm. This plasticity, which applies as well to other life history patterns, likely contributes to the species’ ecological success and persistence across annual- to millennial-scale contrasting sea ice regimes.

From field to sky: measurement and modeling of transgenic switchgrass pollen dispersal in the atmosphere - Manu Nimmala; Hope A. Gruszewski; Regina Hanlon; Landon Bilyeu; Tyler Newton; Jessica Stockdale; Reginald J. Millwood; Charles Neal Stewart; Craig W. Powers; Shane D. Ross; Hosein Foroutan; David G. Schmale III (Environmental Monitoring and Assessment, 2026)
Accurate tracking and measurement of pollen dispersal in the atmosphere are essential for assessing cross-pollination risks, particularly in the case of genetically engineered (GE) crops. We conducted a series of unique release-recapture field studies with GE switchgrass in Oliver Springs, TN, USA. Two hundred transgenic switchgrass plants ( Panicum virgatum L. “Performer”) were planted at the center of a clear-cut field, with one block of 100 plants expressing orange fluorescent protein (OFP) under a switchgrass ubiquitin promoter (PvUBI1) and another block of 100 plants expressing OFP driven by a maize pollen-specific promoter (Zm13). Pollen was sampled from the atmosphere using fixed (ground-based) and mobile (drone-based) sampling devices at different distances from the source field, with Lagrangian stochastic dispersal simulations run for sampling periods using high-resolution wind measurements. The pollen emission rate was estimated by combining simulated and measured pollen concentrations, and strong diurnal trends were observed. Diurnal emission rate trends were positively correlated with wind speed, temperature, and vapor pressure deficit, while negatively correlated with relative humidity. In low-wind meandering conditions, incorporating changing wind direction into the dispersal modeling improved pollen emission rate estimation and model-measurement comparisons. This study assesses the effectiveness of high- and low-volume pollen samplers in relation to source strength up to 1 km from the source, enhancing understanding of pollen measurement techniques. Additionally, it is a proof-of-concept for drone-based pollen sampling and GMO pollen tracking using fluorescence measurements. Results from our experiments have significant implications for cross-pollination risk assessment, prediction, and management of airborne allergens.

Drought conditioning influences conifer seedling height but not survival three growing seasons after planting - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; David L.R. Affleck; Andrew J. Larson (Forest Ecology and Management, 2026)

Corrigendum to ‘Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control’ [Aquaculture Volume 622 15 July 2026 744046] - Jessica Hintzsche; Lorenzo Vincenzo Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

EPR characterization of a metal-binding site in RquA - Rachelle K. Stowell; Trilok Neupane; Kristian C. Mankiller; Tanner L. Manning; Lily N. Boercker; Charlotte V. DiGaetano; Lauren R. Gotshall; Maegan N. Burke; Andrew Ozarowski; Eric E. Ross; David N. Langelaan; Jennifer N. Shepherd; et al. (JBIC Journal of Biological Inorganic Chemistry, 2026)

Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control - Jessica Hintzsche; Lorenzo V. Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly S. Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

Immune divergence in rainbow trout lines selectively bred for F. psychrophilum resistance or susceptibility revealed by challenge with Weissella tructae - Gregory D. Wiens; Christopher C. Chadwick; Keira Osbourn; Qin Fu; Ross M. Reid; Travis Moreland; Timothy J. Welch; Timothy D. Leeds; David P. Marancik (Fish & Shellfish Immunology, 2026)

Mineral Stabilization Slows Losses of Peatland Carbon Following Long‐Term Drainage for Agriculture - Katy J. Faulkner; Katerina Georgiou; David A. Coomes; Philippa Ascough; Anna Basford; Rodney G. O. Burton; Romy Copley; Emma Keerberg; Alanie Lapina; Kimber Moreland; Christopher Evans; Ross Morrison; et al. (Global Change Biology, 2026)
Cultivated peatlands are a major CO 2 emission source, but the processes that regulate the decomposition of drained peat are debated, especially as drained peat becomes increasingly shallow. Many cultivated peatlands are underlain by a mineral soil layer. Surface subsidence, oxidation and tillage reduce the peat thickness, which intermixes peat with minerals as peat is lost. A key question is whether this mixing can reduce emissions by making soil organic carbon (SOC) more stable by transforming particulate organic carbon (POC)—which dominates the carbon stock in deep drained peatlands and is readily accessible to microbial decomposers—into mineral‐associated organic carbon (MAOC), which is less accessible to decomposers. To explore this question, we surveyed ten sites across the East Anglian Fens in England, a once extensive (~3900 km 2 ) peatland landscape that has been drained for cultivation since the mid‐seventeenth century. We used variation in cultivation to establish a peat loss gradient to evaluate how topsoil SOC (0–40 cm) and its forms change as peat is lost. As the peat was lost, the soils became rich in minerals (rising from 46% to 88% silt+clay content), resulting in an initial 11‐fold rise in newly‐formed MAOC, but a monotonic decline and near‐total loss of POC. POC turnover times were 3158 ± 62 years, indicative of peat, and POC was always older than MAOC; consequently, microbially‐processed peat along with gradual contributions of recently fixed carbon were sources of MAOC. A four‐month laboratory incubation showed that the MAOC:POC ratio was negatively correlated with respiration. We conclude that long‐term carbon retention via MAOC formation has the potential to reduce carbon loss from degraded, mineral‐mixed peatlands. However, because this MAOC pool is itself vulnerable to loss under continued agricultural drainage, this mechanism is expected to slow rather than halt long‐term soil carbon loss from drained peatlands.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Regional Nasal Drug Deposition in Pediatric vs. Adult Models: In vitro Insights into User Technique and Breathing Patterns Sensitivity - Mohammad Hejazi; Xiomara Owen; David J. Edwards; Michael Hindle; Worth Longest; Theodore Schuman; Ross Walenga; Steven Chopski; Anubhav Kaviratna; Bryan Newman; Laleh Golshahi (Pharmaceutical Research, 2026)
Purpose Although in vitro studies recommended for establishing bioequivalence of locally acting nasal suspension products provide useful information regarding product performance, currently they are not designed to fully account for variability introduced by patient-specific factors such as administration technique and breathing patterns. This limitation, combined with ethical and practical challenges in conducting pediatric clinical trials, creates a knowledge gap in understanding age-related differences in nasal drug delivery. Methods Anatomically realistic in vitro nasal models representing an average child and adult, in terms of total drug delivery to the sites of intended action posterior to nasal valve, were used to investigate the sensitivity of regional nasal drug deposition to variations in administration parameters and breathing conditions. Three breathing conditions were evaluated: breath hold, gentle sniffing, and vigorous sniffing. Administration parameters were varied using a Box-Behnken experimental design. Results Results showed that for commercially available nasal sprays, breathing patterns did not significantly affect drug delivery in the adult model, but extreme conditions (no breathing vs. vigorous sniffing) caused significant differences in anterior deposition in the child model. Differences between gentle sniffing and the other conditions were not statistically significant. The sensitivity analysis revealed that in vitro drug deposition patterns differ between child and adult nasal cavities under identical user parameter variations, and variable importance differed across nasal cavity regions. Conclusions This study demonstrates the potential for targeted drug delivery by enabling the identification of the optimal administration parameters to achieve desired outcomes, such as enhanced drug deposition in specific nasal regions.

A phylogenomic and metagenomic meta-analysis of bacterial diversity in the phyllosphere lifts a veil on hyphomicrobiales dark matter - Jean-Baptiste Leducq; Louis-Philippe St-Amand; David Ross; Steven W. Kembel (Systematic and Applied Microbiology, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Motorways, drought and wildfire: do they shape trajectories of arboreal mammal populations in eastern Australia? - Ross L. Goldingay; David Rohweder; Brendan D. Taylor; Luke Andrews; Nirvarna Steel; Nick Priest; Will McDonald (Biodiversity and Conservation, 2026)
Motorways have the potential to create barriers to the movement of wildlife, increase mortality and cause edge effects, producing declines in abundance in nearby habitat. We investigated the response of six nocturnal arboreal mammal species to the construction of a new motorway in eastern Australia: five gliding species (three small, 500 g) and one generalist non-gliding species (4 kg). The two large gliding species are listed nationally as threatened. We employed dynamic occupancy modelling using repeat surveys at 75 sites over an 8-year period, beginning one year before motorway construction commenced. We predicted that if species were adversely affected by the motorway, then the probability of occupancy and/or detection should decline at sites near ( 0.5) across all years suggesting there was no influence due to the motorway. The probability of occupancy and detection in the large gliding species declined across the eight years. These findings support the hypothesis that differences in life history (slow vs. fast) among the gliding mammals influence their response to disturbances (landscape change, drought, wildfire). This suggests a much longer period to assess recovery is needed for species with a slow life history.

Top‐Down and Bottom‐Up Processes Jointly Explain Mesopredator Movement and Foraging Ecology - Katie R. N. Florko; Tyler R. Ross; Steven H. Ferguson; Joseph M. Northrup; Martyn E. Obbard; Gregory W. Thiemann; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2026)
Prey availability and predation risk drive animal distribution, movement, and foraging ecology, yet studies rarely analyse multiple predator–prey levels together. Understanding how predators optimise risk–reward tradeoffs is important for species conservation and management, especially in systems facing extreme ecosystem change. We examined how top‐down (modelled polar bear habitat selection) and bottom‐up (modelled fish diversity) processes influence the habitat selection, movement, and foraging behaviour of 26 ringed seals (greater than 70,000 dives and 10,000 locations over 877 seal days). Our results suggest that polar bears spatially restrict seal movements and reduce the time seals spend foraging, potentially decreasing foraging success. Seals were more likely to be present and dive longer in high‐predation risk areas when prey diversity was high. Further, seal habitat selection models excluding polar bears overestimated core space use. These findings illustrate the dynamic tradeoffs that mesopredators make when balancing predation risk and resource acquisition.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

87Sr/86Sr isotope ratios in soils, vine leaves, grapes and wines of the Italian volcanic districts authenticate their respective terroirs - Bruna Saar de Almeida; David Widory; Massimo D'Antonio; Mariano Mercurio; Vincenzo Mora; Ross Stevenson; Lorenzo Fedele (Food Control, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Taphonomy of soft-tissue preservation in ferricrete at the McGraths Flat Lagerstätte - Tara Djokic; Patrick M. Smith; Jeff R. Havig; Michael Frese; Paulo Vasconcelos; Jochen Brocks; Michael Ellwood; David J. Cantrill; Dayna McGeeney; Ross Pogson; Chris Ryan; Yu Wang; et al. (Gondwana Research, 2026)

Impacts of rotation, tillage, cover cropping, and drainage on soil health in soybean-based cropping systems: Evidence from 4–50-year trials across the US - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Chad D. Lee; David Jordan; Hanna J. Poffenbarger; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Agriculture, Ecosystems & Environment, 2026)

Refining Irish breeding goals for sustainable suckler systems through the incorporation of an enteric methane emissions trait - Clodagh V. Ryan; Deirdre C. Purfield; David Kenny; Paul Crosson; Ross D. Evans (Livestock Science, 2025)

Shining a light on hidden PFAS: Development of a UV-reducible organic fluorine assay for the rapid screening of PFAS in AFFF, water, soils, and commercial products - David Patch; Natalia O’Connor; Ellie Ahmed; Erika Houtz; Michael J. Bentel; Ian Ross; Jennifer Scott; Iris Koch; Kela Weber (Journal of Hazardous Materials, 2025)

Commercial biostimulant seed treatments showed minimal impact on soybean seed yield across the United States - Fabiano Colet; Spyridon Mourtzinis; Rachel A. Vann; Seth Naeve; Shawn P. Conley; Emma G. Matcham; Andre Borja Reis; Hans Kandel; David Moseley; Michael Plumblee; Eros Francisco; Giovani Preza Fontes; et al. (Field Crops Research, 2025)

A QSP PDE model of ADC transport and kinetics in a growing or shrinking tumor - David S. Ross; Antonio Cabal (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

The first report of Hematodinium perezi genotype I infection of Chinese mitten crab (Eriocheir sinensis) from the River Thames, UK - Rose C. Kerr; Hamish J. Small; David Bass; Wafa S. Al Arimi; Stuart Ross; Roland Pevsner; Bryony Williams; Ronny van Aerle; Grant Stentiford; Kelly Bateman (Journal of Invertebrate Pathology, 2025)

Morphological and physiological response of conifer seedlings to drought conditioning - Anna C. Ross; Jeremiah R. Pinto; Justin S. Crotteau; Alex Goke; Cara R. Nelson; David L. R. Affleck; Andrew J. Larson (New Forests, 2025)

100 Years of Penaeid Domestication and Meta-Analysis of Breeding Traits - Shengjie Ren; José M. Yáñez; Ricardo Perez-Enriquez; Morten Rye; Ross D. Houston; David A. Hurwood; Jose R. Gonzalez-Galaviz; Marcela Salazar; Adriana Max-Aguilar; Nicholas M. Wade; Dean R. Jerry (Reviews in Fisheries Science & Aquaculture, 2025)

Investigating detrital apatite from the Castlemaine Group, central Victoria, to unravel sources and multi-cycle sedimentation - Luke Tylkowski; Caroline Tiddy; David Giles; Ross Cayley; Adrienne Brotodewo; Robert Thorne; Wessley Edgar (Gondwana Research, 2025)

Comparative analysis of the temporal abundance of the epiphytic pest, Melanothamnus thailandicus, affecting farmed Kappaphycus striatus: Visual and molecular detection approaches - Joseph P. Faisan; Rema C. Sibonga; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Jonalyn P. Mateo; Janina Brakel; Juliet Brodie; Georgia M. Ward; David Bass; Stuart Ross; Grant D. Stentiford; Claire Gachon; et al. (Journal of Applied Phycology, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Soybean yield response to management practices (4–40 years) and soil health parameters - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Spyridon Mourtzinis; Chad D. Lee; David Jordan; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Field Crops Research, 2025)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

A user’s guide to coral reef restoration terminologies - David J. Suggett; Elizabeth A. Goergen; Megan Fraser; Margaux Y. Hein; Whitney Hoot; Ian McLeod; Phanor H. Montoya-Maya; Tom Moore; Andrew M. Ross; Tali Vardi (Coral Reefs, 2025)
Global coral reef restoration efforts continue to diversify in approach, location, and socio-ecological context. In parallel, vocabulary has evolved such that practitioners, scientists, policy makers, communicators, and investors must navigate an increasingly confusing set of terms that are inconsistently defined. Precision around terms and definitions is an important attribute underpinning the rate and extent with which restoration can scale. However, in contrast with more established ecological restoration fields, coral reef restoration lacks a formal lexicon for its core approaches and processes. Here we synthesize, distill, and clarify a core lexicon proposed for coral reef restoration. We navigate readers systematically through terms used for various coral reef restoration approaches, project planning and intent, process workflows, and biological material. We also consider vague terms commonly used that present challenges to singularly define. While we expect this proposed lexicon to continue to evolve, we offer an important first step toward more integrated communications around coral reef restoration.

Correction: Optimising Instrumented Mouthguard Data Analysis: Video Synchronisation Using a Cross-correlation Approach - James Tooby; Steve Rowson; Kevin Till; David Allan; Melanie Dawn Bussey; Dario Cazzola; Éanna Falvey; Kenzie Friesen; Andrew J. Gardner; Cameron Owen; Gregory Roe; Thomas Sawczuk; et al. (Annals of Biomedical Engineering, 2025)

Optimising Instrumented Mouthguard Data Analysis: Video Synchronisation Using a Cross-correlation Approach - James Tooby; Steve Rowson; Kevin Till; David Allan; Melanie Dawn Bussey; Dario Cazzola; Éanna Falvey; Kenzie Friesen; Andrew J. Gardner; Cameron Owen; Gregory Roe; Thomas Sawczuk; et al. (Annals of Biomedical Engineering, 2025)
Purpose Head acceleration events (HAEs) are a growing concern in contact sports, prompting two rugby governing bodies to mandate instrumented mouthguards (iMGs). This has resulted in an influx of data imposing financial and time constraints. This study presents two computational methods that leverage a dataset of video-coded match events: cross-correlation synchronisation aligns iMG data to a video recording, by providing playback timestamps for each HAE, enabling analysts to locate them in video footage; and post-synchronisation event matching identifies the coded match event (e.g. tackles and ball carries) from a video analysis dataset for each HAE, this process is important for calculating the probability of match events resulting in HAEs. Given the professional context of iMGs in rugby, utilising commercial sources of coded match event datasets may expedite iMG analysis. Methods Accuracy and validity of the methods were assessed via video verification during 60 rugby matches. The accuracy of cross-correlation synchronisation was determined by calculating synchronisation error, whilst the validity of post-synchronisation event matching was evaluated using diagnostic accuracy measures (e.g. positive predictive value [PPV] and sensitivity). Results Cross-correlation synchronisation yielded mean synchronisation errors of 0.61–0.71 s, with all matches synchronised within 3 s’ error. Post-synchronisation event matching achieved PPVs of 0.90–0.95 and sensitivity of 0.99–1.00 for identifying correct match events for SAEs. Conclusion Both methods achieved high accuracy and validity with the data sources used in this study. Implementation depends on the availability of a dataset of video-coded match events; however, integrating commercially available video-coded datasets offers the potential to expedite iMG analysis, improve feedback timeliness, and augment research analysis.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

From rock to bottle: strontium isotopes (87Sr/86Sr) as indicator of provenance for the volcanic wines of altitude from São Joaquim, southern Brazil - Erico Albuquerque Santos; Luana Moreira Florisbal; Ross Stevenson; David Widory; Denilson Dortzbach; Bruna Saar de Almeida; Arcângelo Loss (CATENA, 2025)

Practical limits of current technologies in removing per- and polyfluoroalkyl substances from fire suppression systems - Dung Nguyen; Christopher Bellona; Adria Lau; John Stults; Hayley Andrews; David Jones; David Megson; Ian Ross (Journal of Hazardous Materials, 2025)

Food system adaptation and maintaining trade could mitigate global famine in abrupt sunlight reduction scenarios - Morgan Rivers; Michael Hinge; Kevin Rassool; Simon Blouin; Florian U. Jehn; Juan B. García Martínez; Vasco Amaral Grilo; Victor Jaeck; Ross J. Tieman; James Mulhall; Talib E. Butt; David C. Denkenberger (Global Food Security, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Non-targeted analysis reveals hundreds of per- and polyfluoroalkyl substances (PFAS) in UK freshwater in the vicinity of a fluorochemical plant - David Megson; Daniel Niepsch; Jonathan Spencer; Claudio dos Santos; Hannah Florance; Cecilia L. MacLeod; Ian Ross (Chemosphere, 2024)

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Extra-terrestrial mantle samples: Rare Earth Element variations and evidence for melt metasomatism in ureilite meteorites - Hilary Downes; David W. Mittlefehldt; Aidan J. Ross; Cin-Ty Lee (Lithos, 2024)

Gauging the threat of invasive species to UNESCO world heritage sites relative to other anthropogenic threats - Marc William Cadotte; Mohamed Alabbasi; Sara Akib; Pruthuvie Chandradhas; Joanne Gui; Kelly Huang; Adrian Li; David M. Richardson; Ross T. Shackleton (Biological Invasions, 2024)

Geomorphological controls on estuary hydrodynamics with implications for diatom blooms in deglaciated coastal areas - Taylor Bailey; Lauren Ross; Nicholas Tiner; Sean M.C. Smith; Iván Ernesto Pérez Santos; Antonio Ramos; Alejandro García Mendoza; David Miller (Science of The Total Environment, 2024)

Advancing PFAS characterization: Development and optimization of a UV-H2O2-TOP assay for improved PFCA chain length preservation and organic matter tolerance - David Patch; Natalia O'Connor; Ellie Ahmed; Erika Houtz; Michael Bentel; Ian Ross; Jennifer Scott; Iris Koch; Kela Weber (Science of The Total Environment, 2024)

Advances in understanding Lepidoptera cold tolerance - Hamzeh Izadi; Ross N. Cuthbert; Phillip J. Haubrock; David Renault (Journal of Thermal Biology, 2024)

The influence of seawater pCO2 and temperature on the amino acid composition and aragonite CO3 disorder of coral skeletons - Nicola Allison; Phoebe Ross; Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Celeste Kellock; Catherine Cole; Matthieu Clog; David Evans; Chris Hintz; Ken Hintz; Adrian A. Finch (Coral Reefs, 2024)
Coral skeletons are composites of aragonite and biomolecules. We report the concentrations of 11 amino acids in massive Porites spp. coral skeletons cultured at two temperatures (25 °C and 28 °C) and 3 seawater pCO 2 (180, 400 and 750 µatm). Coral skeletal aspartic acid/asparagine (Asx), glutamic acid/glutamine (Glx), glycine, serine and total amino acid concentrations are significantly higher at 28 °C than at 25 °C. Skeletal Asx, Glx, Gly, Ser, Ala, L-Thr and total amino acid are significantly lower at 180 µatm seawater pCO 2 compared to 400 µatm, and Ser is reduced at 180 µatm compared to 750 µatm. Concentrations of all skeletal amino acids are significantly inversely related to coral calcification rate but not to calcification media pH. Raman spectroscopy of these and additional specimens indicates that CO 3 disorder in the skeletal aragonite lattice is not affected by seawater pCO 2 but decreases at the higher temperature. This is contrary to observations in synthetic aragonite where disorder is positively related to the aragonite precipitation rate mediated by either increasing temperature (this study) or increasing Ω (this study and a previous report) and to the concentration of amino acid in the precipitation media (a previous report). We observe no significant relationship between structural disorder and coral calcification rate or skeletal [amino acid]. Both temperature and seawater pCO 2 can significantly affect skeletal amino acid composition, and further work is required to clarify how environmental change mediates disorder.

Maternal pre-pregnancy BMI influences the associations between bisphenol and phthalate exposures and maternal weight changes and fat accumulation - Nathalie Irvine; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Jiaying Liu; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey; Gillian England-Mason; B.J. Kaplan; C.J. Field; et al. (Environmental Research, 2024)

Temporal variation in the incidence of seaweed health problems affecting farmed Kappaphycus striatus in relation to environmental conditions in shallow waters - Joseph P. Faisan; Rema C. Sibonga; Jonalyn P. Mateo; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Vicente T. Balinas; Janina Brakel; David Bass; Stuart Ross; Grant D. Stentiford; Juliet Brodie; Georgia M. Ward; et al. (Journal of Applied Phycology, 2024)

Biological invasions as burdens to primary economic sectors - Anna J. Turbelin; Emma J. Hudgins; Jane A. Catford; Ross N. Cuthbert; Christophe Diagne; Melina Kourantidou; David Roiz; Franck Courchamp (Global Environmental Change, 2024)

A review of the safety evidence on recombinant human lactoferrin for use as a food ingredient - Roma Vishwanath-Deutsch; David C. Dallas; Pamela Besada-Lombana; Laura Katz; Dietrich Conze; Claire Kruger; Anthony J. Clark; Ross Peterson; Carrie-Anne Malinczak (Food and Chemical Toxicology, 2024)

The effects of different types of organisational workplace mental health interventions on mental health and wellbeing in healthcare workers: a systematic review - Birgit Aust; Caleb Leduc; Johanna Cresswell-Smith; Clíodhna O’Brien; Reiner Rugulies; Mallorie Leduc; Doireann Ni Dhalaigh; Arilda Dushaj; Naim Fanaj; Daniel Guinart; Margaret Maxwell; Hanna Reich; et al. (International Archives of Occupational and Environmental Health, 2024)
Objective To determine if and which types of organisational interventions conducted in small and medium size enterprises (SMEs) in healthcare are effective on mental health and wellbeing. Methods Following PRISMA guidelines, we searched six scientific databases, assessed the methodological quality of eligible studies using QATQS and grouped them into six organisational intervention types for narrative synthesis. Only controlled studies with at least one follow-up were eligible. Results We identified 22 studies (23 articles) mainly conducted in hospitals with 16 studies rated of strong or moderate methodological quality. More than two thirds (68%) of the studies reported improvements in at least one primary outcome (mental wellbeing, burnout, stress, symptoms of depression or anxiety), most consistently in burnout with eleven out of thirteen studies. We found a strong level of evidence for the intervention type “Job and task modifications” and a moderate level of evidence for the types “Flexible work and scheduling” and “Changes in the physical work environment”. For all other types, the level of evidence was insufficient. We found no studies conducted with an independent SME, however five studies with SMEs attached to a larger organisational structure. The effectiveness of workplace mental health interventions in these SMEs was mixed. Conclusion Organisational interventions in healthcare workers can be effective in improving mental health, especially in reducing burnout. Intervention types where the change in the work environment constitutes the intervention had the highest level of evidence. More research is needed for SMEs and for healthcare workers other than hospital-based physicians and nurses.

Activated carbon amendment of sand in the base of a permeable pavement reduces total nitrogen and nitrate leaching - Rixia Zan; Ross Stirling; Adrian Blackburn; Claire Walsh; David Werner (Science of The Total Environment, 2024)

covXtreme : MATLAB software for non-stationary penalised piecewise constant marginal and conditional extreme value models - Ross Towe; Emma Ross; David Randell; Philip Jonathan (Environmental Modelling & Software, 2024)

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Blanford's fox (Vulpes cana) habitat suitability in Saudi Arabia: Insights from camera trapping and ensemble species distribution modelling - J. Philip B. Faure; Marine Drouilly; Alexander E. Botha; Michael D. Ross; J. Andrew Spalton; Mesfer AlHlafi; Carolyn E. Dunford; David R. Mills; Ross De Bruin; Emma Gallacher; Gareth K.H. Mann (Journal of Arid Environments, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

The Tasmanian Tyennan Domain–a structural synthesis and review with tectonic and dynamic implications for continental margin subduction and exhumation - David Ross Gray; M. J. Vicary; A. W. McNeill (Australian Journal of Earth Sciences, 2024)

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Discrepancies between non-native and invasive species classifications - Phillip J. Haubrock; Ross N. Cuthbert; Paride Balzani; Elizabeta Briski; Carlos Cano-Barbacil; Vanessa De Santis; Emma J. Hudgins; Antonín Kouba; Rafael L. Macêdo; Melina Kourantidou; David Renault; Axel E. Rico-Sánchez; et al. (Biological Invasions, 2024)

Opposing genetic patterns of range shifting temperate and tropical gastropods in an area undergoing tropicalisation - Karolina M. Zarzyczny; Michael E. Hellberg; Elena B. Lugli; Moira MacLean; David A. Paz‐García; Marc Rius; Ethan G. Ross; Erick X. Treviño Balandra; James Vanstone; Suzanne T. Williams; Phillip B. Fenberg (Journal of Biogeography, 2024)
Aim The poleward range expansion of tropical species, and range contraction of temperate species (known as tropicalisation) has mainly been studied from an ecological perspective, with little research on its genetic consequences. Here, we used distributional and genetic data to document the consequences of tropicalisation in rocky shore gastropods and assess more broadly the future implications of tropicalisation on phylogeographic patterns. Location Nineteen sampling sites along >3000 km of the eastern Pacific rocky intertidal zone, from the tip of the Baja California Peninsula to southern California. Taxon Temperate gastropods: Lottia conus , L. strigatella , Fissurella volcano and Tegula gallina. Tropical gastropods: Fissurella rubropicta , Nerita funiculata and N. scabricosta. Methods We determine historical and modern distributions of tropical and temperate species by combining historical records with current field surveys. Using a section of the cytochrome oxidase subunit I gene, we utilised comparative phylogeography, analysis of molecular variance, F ST pairwise comparison, mismatch distributions of haplotype differences and neutrality tests to detect genetic signatures of tropicalisation and to better understand its consequences. Results We identified range contractions in two temperate species and range expansion in all three tropical species. We detected genetic signatures of range expansion in the tropical species through unimodal distributions of pairwise haplotype differences and strongly negative values for the Fu and Li D and F * statistics. We found population subdivision and phylogeographic breaks in three temperate species, although the geographic location of the breaks differed among species. Main Conclusions Genetic signatures and field surveys indicate recent range expansions in tropical species, supporting tropicalisation along the studied coastline. Conversely, we found phylogeographic breaks in temperate species, suggesting that tropicalisation may cause genetic erosion of evolutionary distinct lineages with range‐contraction. The different locations of the phylogeographic breaks among temperate species suggests that some barriers are species specific.

Advancing PFAS characterization: Enhancing the total oxidizable precursor assay with improved sample processing and UV activation - David Patch; Natalia O'Connor; Taylor Vereecken; Daniel Murphy; Gabriel Munoz; Ian Ross; Caitlin Glover; Jennifer Scott; Iris Koch; Sébastien Sauvé; Jinxia Liu; Kela Weber (Science of The Total Environment, 2024)

Biological, ecological and trophic features of invasive mosquitoes and other hematophagous arthropods: What makes them successful? - David Renault; Stéphane A. P. Derocles; Phillip Haubrock; Frédéric Simard; Ross N. Cuthbert; Claire Valiente-Moro (Biological Invasions, 2024)

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Divergent ecological responses to typhoon disturbance revealed via landscape‐scale acoustic monitoring - Samuel R. P.‐J. Ross; Nicholas R. Friedman; Kenneth L. Dudley; Takuma Yoshida; Masashi Yoshimura; Evan P. Economo; David W. Armitage; Ian Donohue (Global Change Biology, 2024)
Climate change is increasing the frequency, intensity, and duration of extreme weather events across the globe. Understanding the capacity for ecological communities to withstand and recover from such events is critical. Typhoons are extreme weather events that are expected to broadly homogenize ecological dynamics through structural damage to vegetation and longer‐term effects of salinization. Given their unpredictable nature, monitoring ecological responses to typhoons is challenging, particularly for mobile animals such as birds. Here, we report spatially variable ecological responses to typhoons across terrestrial landscapes. Using a high temporal resolution passive acoustic monitoring network across 24 sites on the subtropical island of Okinawa, Japan, we found that typhoons elicit divergent ecological responses among Okinawa's diverse terrestrial habitats, as indicated by increased spatial variability of biological sound production (biophony) and individual species detections. This suggests that soniferous communities are capable of a diversity of different responses to typhoons. That is, spatial insurance effects among local ecological communities provide resilience to typhoons at the landscape scale. Even though site‐level typhoon impacts on soundscapes and bird detections were not particularly strong, monitoring at scale with high temporal resolution across a broad spatial extent nevertheless enabled detection of spatial heterogeneity in typhoon responses. Further, species‐level responses mirrored those of acoustic indices, underscoring the utility of such indices for revealing insight into fundamental questions concerning disturbance and stability. Our findings demonstrate the significant potential of landscape‐scale acoustic sensor networks to capture the understudied ecological impacts of unpredictable extreme weather events.

Characterizing wine terroir using strontium isotope ratios: a review - Bruna Saar de Almeida; Lorenzo Fedele; Massimo D’Antonio; Vincenzo Morra; Mariano Mercurio; Ross Stevenson; David Widory (Isotopes in Environmental and Health Studies, 2023)

Filling the data gaps: Transferring models from data-rich to data-poor deep-sea areas to support spatial management - Amelia E.H. Bridges; David K.A. Barnes; James B. Bell; Rebecca E. Ross; Lizette Voges; Kerry L. Howell (Journal of Environmental Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Island colonisation leads to rapid behavioural and morphological divergence in Anolis lizards - Daniel J. Nicholson; Robert J. Knell; Edita Folfas; Lauren K. Neel; Zachariah Degon; Madeline DuBois; Xochitl Ortiz-Ross; Albert K. Chung; John David Curlis; Timothy J. Thurman; W. Owen McMillan; Trenton W. J. Garner; et al. (Evolutionary Ecology, 2023)

Locally led adaptation: Promise, pitfalls, and possibilities - M. Feisal Rahman; Danielle Falzon; Stacy-ann Robinson; Laura Kuhl; Ross Westoby; Jessica Omukuti; E. Lisa F. Schipper; Karen E. McNamara; Bernadette P. Resurrección; David Mfitumukiza; Md. Nadiruzzaman (Ambio, 2023)
Locally led adaptation (LLA) has recently gained importance against top-down planning practices that often exclude the lived realities and priorities of local communities and create injustices at the local level. The promise of LLA is that adaptation would be defined, prioritised, designed, monitored, and evaluated by local communities themselves, enabling a shift in power to local stakeholders, resulting in more effective adaptation interventions. Critical reflections on the intersections of power and justice in LLA are, however, lacking. This article offers a nuanced understanding of the power and justice considerations required to make LLA useful for local communities and institutions, and to resolve the tensions between LLA and other development priorities. It also contributes to a further refinement of LLA methodologies and practices to better realise its promises. Ultimately, we argue that the utility of the LLA framing in promoting climate justice and empowering local actors needs to be tested empirically.

Environmental DNA clarifies impacts of combined sewer overflows on the bacteriology of an urban river and resulting risks to public health - Rixia Zan; Adrian Blackburn; Jidapa Plaimart; Kishor Acharya; Claire Walsh; Ross Stirling; Chris G. Kilsby; David Werner (Science of The Total Environment, 2023)

Maturity biomarkers predicting storage performance of early-harvested yellow-fleshed kiwifruit identified using integrated multi-omics analysis - Laurie Favre; Donald A. Hunter; Erin M. O’Donoghue; Zoe A. Erridge; Nathanael J. Napier; Jung Cho; Agam Nangul; Kristie O’Donnell; Paul Pidakala; Philip Martin; Sheryl D. Somerfield; Martin Hunt; et al. (Postharvest Biology and Technology, 2023)

City infrastructure ontologies - Heshan Du; Lijun Wei; Vania Dimitrova; Derek Magee; Barry Clarke; Richard Collins; David Entwisle; Mehran Eskandari Torbaghan; Giulio Curioni; Ross Stirling; Helen Reeves; Anthony G. Cohn (Computers, Environment and Urban Systems, 2023)

Using an Accelerated Undergraduate Needs Finding Course to Build Skills, Inspire Confidence, and Promote Interest in Health Technology Innovation - Lyn Denend; Susie Spielman; Ross Venook; Ravinder D. Pamnani; David Camarillo; James Wall; Joseph Towles (Biomedical Engineering Education, 2023)
Many undergraduate educational experiences in biomedical design lack clinical immersion-based needs finding training for students. Convinced of the merits of this type of training for undergraduates, but unable to offer a quarter-long course due to faculty and administrative constraints, we developed an accelerated block-plan course, during which students were dedicated solely to our class for 3 weeks. The course focused on the earliest stages of the health technology innovation process—conducting effective clinical observations and performing comprehensive need research and screening. We grounded the course in experiential learning theory (with hands-on, collaborative, and immersive experiences) and constructivist learning theory (where students integrated prior knowledge with new material on need-driven innovation). This paper describes the design of this intensive block-plan course and the teaching methods intended to support the achievement of five learning objectives. We used pre- and post-course surveys to gather self-reported data about the effect of the course on student learning. Despite the accelerated format, we saw statistically significant gains for all but one sub-measure across the learning objectives. Our experience supports key benefits of the block-plan model, and the results indicate that specific course design choices were effective in achieving positive learning outcomes. These design decisions include (1) opportunities for students to practice observations before entering the clinical setting; (2) a framework for the curriculum that reinforced important concepts iteratively throughout the program; (3) balanced coverage of preparation, clinical immersion, and need research; (4) extensive faculty and peer coaching; and (5) providing hands-on prototyping opportunities while staying focused on need characterization rather than solution development. Based on our experience, we expect that this model is replicable across institutions with limited bandwidth to support clinical immersion opportunities.

Methoxypyrazine concentrations in the grape bunch rachis of Vitis vinifera L. Cv Shiraz: Influence of rootstock, region and light - Ross D. Sanders; Paul K. Boss; Dimitra L. Capone; Catherine M. Kidman; Sue Maffei; David W. Jeffery (Food Chemistry, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Soybean yield response to nitrogen and sulfur fertilization in the United States: contribution of soil N and N fixation processes - Luiz Felipe A. Almeida; Adrian Correndo; Jeremy Ross; Mark Licht; Shaun Casteel; Maninder Singh; Seth Naeve; Rachel Vann; Jose Bais; Hans Kandel; Laura Lindsey; Shawn Conley; et al. (European Journal of Agronomy, 2023)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Seismically-induced down-sagging structures in tephra layers (tephra-seismites) preserved in lakes since 17.5 cal ka, Hamilton lowlands, New Zealand - Max O. Kluger; David J. Lowe; Vicki G. Moon; Jordanka Chaneva; Richard Johnston; Pilar Villamor; Tehnuka Ilanko; Richard A. Melchert; Rolando P. Orense; Remedy C. Loame; Nic Ross (Sedimentary Geology, 2023)

Estimation of associated values from conditional extreme value models - Ross Towe; David Randell; Jennifer Kensler; Graham Feld; Philip Jonathan (Ocean Engineering, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

A new approach to define an economically important fish as an umbrella flagship species to enhance collaborative stakeholder-management agency habitat conservation - JoEllen K. Wilson; Philip W. Stevens; David A. Blewett; Ross Boucek; Aaron J. Adams (Environmental Biology of Fishes, 2023)

Seasonal differences in softening of early-harvested ‘Royal Gala’ apple fruit are correlated with at-harvest biomarkers indicative of abiotic stress responses - Laurie Favre; Donald A. Hunter; Zoe A. Erridge; Nathanael J. Napier; Matt Punter; Bridie Carr; Anna Tattersall; Jason W. Johnston; Julian A. Heyes; Ross E. Lill; David A. Brummell (Postharvest Biology and Technology, 2023)

Constant-temperature predictions underestimate growth of a fungal amphibian pathogen under individual host thermal profiles - Sasha E. Greenspan; Elizabeth A. Roznik; Lexie Edwards; Richard Duffy; Lee Berger; Deborah S. Bower; David A. Pike; Lin Schwarzkopf; Ross A. Alford (Journal of Thermal Biology, 2023)

Biochar benefits carbon off-setting in blue-green infrastructure soils - A lysimeter study - Jiaqian Wang; David A.C. Manning; Ross Stirling; Elisa Lopez-Capel; David Werner (Journal of Environmental Management, 2023)

Chemostratigraphic and mineralogical examination of the Kilwa Group claystones, coastal Tanzania: An alternative approach to refine the lithostratigraphy - Ross McCabe; Christopher J. Nicholas; Bill Fitches; David Wray; Tim Pearce (Journal of African Earth Sciences, 2023)

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

Early‐life seasonal, weather and social effects on telomere length in a wild mammal - Sil H. J. van Lieshout; Elisa P. Badás; Julius G. Bright Ross; Amanda Bretman; Chris Newman; Christina D. Buesching; Terry Burke; David W. Macdonald; Hannah L. Dugdale (Molecular Ecology, 2022)
Early‐life environmental conditions can provide a source of individual variation in life‐history strategies and senescence patterns. Conditions experienced in early life can be quantified by measuring telomere length, which can act as a biomarker of survival probability in some species. Here, we investigate whether seasonal changes, weather conditions and group size are associated with early‐life and/or early‐adulthood telomere length in a wild population of European badgers ( Meles meles ). We found substantial intra‐annual changes in telomere length during the first 3 years of life, where within‐individual effects showed shorter telomere lengths in the winter following the first spring and a trend for longer telomere lengths in the second spring compared to the first winter. In terms of weather conditions, cubs born in warmer, wetter springs with low rainfall variability had longer early‐life (3–12 months old) telomeres. Additionally, cubs born in groups with more cubs had marginally longer early‐life telomeres, providing no evidence of resource constraint from cub competition. We also found that the positive association between early‐life telomere length and cub survival probability remained when social and weather variables were included. Finally, after sexual maturity, in early adulthood (i.e., 12–36 months) we found no significant association between same‐sex adult group size and telomere length (i.e., no effect of intrasexual competition). Overall, we show that controlling for seasonal effects, which are linked to food availability, is important in telomere length analyses, and that variation in telomere length in badgers reflects early‐life conditions and also predicts first year cub survival.

Seasonal gain in body condition of foraging humpback whales along the Western Antarctic Peninsula - K. C. Bierlich; Joshua Hewitt; Robert S. Schick; Logan Pallin; Julian Dale; Ari S. Friedlaender; Fredrik Christiansen; Kate R. Sprogis; Allison H. Dawn; Clara N. Bird; Gregory D. Larsen; Ross Nichols; et al. (Frontiers in Marine Science, 2022)
Most baleen whales are capital breeders that use stored energy acquired on foraging grounds to finance the costs of migration and reproduction on breeding grounds. Body condition reflects past foraging success and can act as a proxy for individual fitness. Hence, monitoring the seasonal gain in body condition of baleen whales while on the foraging grounds can inform how marine mammals support the costs of migration, growth, and reproduction, as well as the nutritional health of the overall population. Here, we use photogrammetry from drone-based imagery to examine how the body condition of humpback whales ( Megaptera novaeangliae ) changed over the foraging season (November to June) along the Western Antarctic Peninsula (WAP) from 2017 to 2019. This population (IWC stock G) is recovering from past whaling and is growing rapidly, providing an opportunity to study how whales store energy in a prey-rich environment. We used a body area index (BAI) to estimate changes in body condition and applied a Bayesian approach to incorporate measurement uncertainty associated with different drone types used for data collection. We used biopsy samples to determine sex and pregnancy status, and a length-based maturity classification to assign reproductive classes ( n = 228; calves = 31, juveniles = 82, lactating females = 31, mature males = 12, mature unknown sex = 56, non-pregnant females = 12, pregnant females = 3, pregnant & lactating females = 1). Average BAI increased linearly over the feeding season for each reproductive class. Lactating females had lower BAI compared to other mature whales late in the season, reflecting the high energetic costs of nursing a calf. Mature males and non-pregnant females had the highest BAI values. Calves and juvenile whales exhibited an increase in BAI but not structural size (body length) over the feeding season. The body length of lactating mothers was positively correlated with the body length of their calves, but no relationship was observed between the BAI of mothers and their calves. Our study establishes a baseline for seasonal changes in the body condition for this humpback whale population, which can help monitor future impacts of disturbance and climate change.

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Toward a decade of ocean science for sustainable development through acoustic animal tracking - Josep Alós; Kim Aarestrup; David Abecasis; Pedro Afonso; Alexandre Alonso‐Fernandez; Eneko Aspillaga; Margarida Barcelo‐Serra; Jonathan Bolland; Miguel Cabanellas‐Reboredo; Robert Lennox; Ross McGill; Aytaç Özgül; et al. (Global Change Biology, 2022)
The ocean is a key component of the Earth's dynamics, providing a great variety of ecosystem services to humans. Yet, human activities are globally changing its structure and major components, including marine biodiversity. In this context, the United Nations has proclaimed a Decade of Ocean Science for Sustainable Development to tackle the scientific challenges necessary for a sustainable use of the ocean by means of the Sustainable Development Goal 14 (SDG14). Here, we review how Acoustic animal Tracking, a widely distributed methodology of tracking marine biodiversity with electronic devices, can provide a roadmap for implementing the major Actions to achieve the SDG14. We show that acoustic tracking can be used to reduce and monitor the effects of marine pollution including noise, light, and plastic pollution. Acoustic tracking can be effectively used to monitor the responses of marine biodiversity to human‐made infrastructures and habitat restoration, as well as to determine the effects of hypoxia, ocean warming, and acidification. Acoustic tracking has been historically used to inform fisheries management, the design of marine protected areas, and the detection of essential habitats, rendering this technique particularly attractive to achieve the sustainable fishing and spatial protection target goals of the SDG14. Finally, acoustic tracking can contribute to end illegal, unreported, and unregulated fishing by providing tools to monitor marine biodiversity against poachers and promote the development of Small Islands Developing States and developing countries. To fully benefit from acoustic tracking supporting the SDG14 Targets, trans‐boundary collaborative efforts through tracking networks are required to promote ocean information sharing and ocean literacy. We therefore propose acoustic tracking and tracking networks as relevant contributors to tackle the scientific challenges that are necessary for a sustainable use of the ocean promoted by the United Nations.

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

Massive economic costs of biological invasions despite widespread knowledge gaps: a dual setback for India - Alok Bang; Ross N. Cuthbert; Phillip J. Haubrock; Romina D. Fernandez; Desika Moodley; Christophe Diagne; Anna J. Turbelin; David Renault; Tatenda Dalu; Franck Courchamp (Biological Invasions, 2022)
Biological invasions are one of the top drivers of the ongoing biodiversity crisis. An underestimated consequence of invasions is the enormity of their economic impacts. Knowledge gaps regarding economic costs produced by invasive alien species (IAS) are pervasive, particularly for emerging economies such as India—the fastest growing economy worldwide. To investigate, highlight and bridge this gap, we synthesised data on the economic costs of IAS in India. Specifically, we examine how IAS costs are distributed spatially, environmentally, sectorally, taxonomically, temporally, and across introduction pathways; and discuss how Indian IAS costs vary with socioeconomic indicators. We found that IAS have cost the Indian economy between at least US$ 127.3 billion to 182.6 billion (Indian Rupees ₹ 8.3 trillion to 11.9 trillion) over 1960–2020, and these costs have increased with time. Despite these massive recorded costs, most were not assigned to specific regions, environments, sectors, cost types and causal IAS, and these knowledge gaps are more pronounced in India than in the rest of the world. When costs were specifically assigned, maximum costs were incurred in West, South and North India, by invasive alien insects in semi-aquatic ecosystems; they were incurred mainly by the public and social welfare sector, and were associated with damages and losses rather than management expenses. Our findings indicate that the reported economic costs grossly underestimate the actual costs, especially considering the expected costs given India’s population size, gross domestic product and high numbers of IAS without reported costs. This cost analysis improves our knowledge of the negative economic impacts of biological invasions in India and the burden they can represent for its development. We hope this study motivates policymakers to address socio-ecological issues in India and launch a national biological invasion research programme, especially since economic growth will be accompanied by greater impacts of global change.

Surprisingly high economic costs of biological invasions in protected areas - Desika Moodley; Elena Angulo; Ross N. Cuthbert; Brian Leung; Anna Turbelin; Ana Novoa; Melina Kourantidou; Gustavo Heringer; Phillip J. Haubrock; David Renault; Marine Robuchon; Jean Fantle-Lepczyk; et al. (Biological Invasions, 2022)
Biological invasions are one of the main threats to biodiversity within protected areas (PAs) worldwide. Meanwhile, the resilience of PAs to invasions remains largely unknown. Consequently, providing a better understanding of how they are impacted by invasions is critical for informing policy responses and optimally allocating resources to prevention and control strategies. Here we use the InvaCost database to address this gap from three perspectives: (i) characterizing the total reported costs of invasive alien species (IAS) in PAs; (ii) comparing mean observed costs of IAS in PAs and non-PAs; and (iii) evaluating factors affecting mean observed costs of IAS in PAs. Our results first show that, overall, the reported economic costs of IAS in PAs amounted to US$ 22.24 billion between 1975 and 2020, of which US$ 930.61 million were observed costs (already incurred) and US$ 21.31 billion were potential costs (extrapolated or predicted). Expectedly, most of the observed costs were reported for management (73%) but damages were still much higher than expected for PAs (24%); in addition, the vast majority of management costs were reported for reactive, post-invasion actions (84% of management costs, focused on eradication and control). Second, differences between costs in PAs and non-PAs varied among continents and environments. We found significantly higher IAS costs in terrestrial PA environments compared to non-PAs, while regionally, Europe incurred higher costs in PAs and Africa and Temperate Asia incurred higher costs in non-PAs. Third, characterization of drivers of IAS costs within PAs showed an effect of environments (higher costs in terrestrial environments), continents (higher in Africa and South America), taxa (higher in invertebrates and vertebrates than plants) and Human Development Index (higher in more developed countries). Globally, our findings indicate that, counterintuitively, PAs are subject to very high costs from biological invasions. This highlights the need for more resources to be invested in the management of IAS to achieve the role of PAs in ensuring the long term conservation of nature. Accordingly, more spatially-balanced and integrative studies involving both scientists and stakeholders are required.

Modelling the damage costs of invasive alien species - Danish A. Ahmed; Emma J. Hudgins; Ross N. Cuthbert; Phillip J. Haubrock; David Renault; Elsa Bonnaud; Christophe Diagne; Franck Courchamp (Biological Invasions, 2022)
The rate of biological invasions is growing unprecedentedly, threatening ecological and socioeconomic systems worldwide. Quantitative understandings of invasion temporal trajectories are essential to discern current and future economic impacts of invaders, and then to inform future management strategies. Here, we examine the temporal trends of cumulative invasion costs by developing and testing a novel mathematical model with a population dynamical approach based on logistic growth. This model characterises temporal cost developments into four curve types (I–IV), each with distinct mathematical and qualitative properties, allowing for the parameterization of maximum cumulative costs, carrying capacities and growth rates. We test our model using damage cost data for eight genera ( Rattus , Aedes , Canis , Oryctolagus , Sturnus , Ceratitis , Sus and Lymantria ) extracted from the InvaCost database—which is the most up-to-date and comprehensive global compilation of economic cost estimates associated with invasive alien species. We find fundamental differences in the temporal dynamics of damage costs among genera, indicating they depend on invasion duration, species ecology and impacted sectors of economic activity. The fitted cost curves indicate a lack of broadscale support for saturation between invader density and impact, including for Canis , Oryctolagus and Lymantria , whereby costs continue to increase with no sign of saturation. For other taxa, predicted saturations may arise from data availability issues resulting from an underreporting of costs in many invaded regions. Overall, this population dynamical approach can produce cost trajectories for additional existing and emerging species, and can estimate the ecological parameters governing the linkage between population dynamics and cost dynamics.

Preserving identity in capture–mark–recapture studies: increasing the accuracy of minimum number alive (MNA) estimates by incorporating inter-census trapping efficiency variation - Julius G. Bright Ross; Chris Newman; Christina D. Buesching; David W. Macdonald (Mammalian Biology, 2022)
Quantifying abundance is often key to understanding ecological and evolutionary processes in wild populations. Despite shortcomings in producing accurate abundance estimates, minimum number alive (MNA) remains a widely used tool, due to its intuitive computation, reliable performance as an abundance indicator, and linkage to individual life-histories. Here, we propose a novel “efficiency-modified” MNA (eMNA) metric, which aims to preserve MNA’s favourable aspects while remedying its flaws, by incorporating (a) growth correlates to back-age individuals first captured as adults, and (b) estimates of undetected persistence beyond last capture based on time-varying capture efficiency. We evaluate eMNA through samplings of a simulated baseline population parameterised using data from a long-term demographic study of European badgers ( Meles meles ), under three different levels of capture efficiency (low; intermediate/“real” based on badger field data; high). We differentiate between eMNA’s performance as an abundance estimator —how well it approximates true abundance (accuracy)—and as an abundance indicator —how tightly it correlates with population abundance and changes thereof (precision). eMNA abundance estimates were negatively biased at all capture efficiencies. However, this bias was negligible at intermediate-to-high capture efficiency, particularly once low-information terminal sampling years (the first year and final three years of simulated studies) were removed. Excluding these years, eMNA under-estimated abundance by only 3.5 badgers (1.5% of population) at intermediate (real) capture efficiencies, and performed as a precise abundance indicator, with half the standard deviation of Cormack–Jolly–Seber probabilistic estimates and proving robust to inter-sampling variation in capture efficiency. Using undetected persistence probabilities to parameterise survival regression, we recreated baseline age-based survival relationships, albeit with some negative bias for under-represented ages. We offer considerations on the continued limitations of using eMNA for abundance estimates, minimum study duration for reliability, the metric’s benefits when individual identity is required, and potential for further improvement.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Building community resilience in a context of climate change: The role of social capital - Esther Carmen; Ioan Fazey; Helen Ross; Melissa Bedinger; Fiona M. Smith; Katrin Prager; Kerri McClymont; David Morrison (Ambio, 2022)
Social capital is considered important for resilience across social levels, including communities, yet insights are scattered across disciplines. This meta-synthesis of 187 studies examines conceptual and empirical understandings of how social capital relates to resilience, identifying implications for community resilience and climate change practice. Different conceptualisations are highlighted, yet also limited focus on underlying dimensions of social capital and proactive types of resilience for engaging with the complex climate change challenge. Empirical insights show that structural and socio-cultural aspects of social capital, multiple other factors and formal actors are all important for shaping the role of social capital for guiding resilience outcomes. Thus, finding ways to work with these different elements is important. Greater attention on how and why outcomes emerge, interactions between factors, approaches of formal actors and different socio-cultural dimensions will advance understandings about how to nurture social capital for resilience in the context of climate change.

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

Sea-Level Rise and the Persistence of Tree Islands in Coastal Landscapes - Michael S. Ross; Susana L. Stoffella; Rosario Vidales; John F. Meeder; David C. Kadko; Leonard J. Scinto; Suresh C. Subedi; Jed R. Redwine (Ecosystems, 2022)

The Scope for Geotourism Based on Regolith in Southwestern Australia—a Theoretical and Practical Perspective - David Newsome; Philip Ladd; Ross Dowling (Geoheritage, 2022)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Palm oil supply chain factors impacting chlorinated precursors of 3-MCPD esters - Soon Huat Tiong; Anusha Nair; Siti Aishah Abd. Wahid; Norliza Saparin; Nur Azwani Ab. Karim; Maizatul Putri Ahmad Sabri; Mohd Zairey Md. Zain; Huey Fang Teh; Ahmad Sarwani Adni; Chin Ping Tan; Oi Ming Lai; See Siang Cheah; et al. (Food Additives & Contaminants: Part A, 2021)

Underwater Light Characteristics of Turbid Coral Reefs of the Inner Central Great Barrier Reef - Ross Jones; Mari-Carmen Pineda; Heidi M. Luter; Rebecca Fisher; David Francis; Wojciech Klonowski; Matthew Slivkoff (Frontiers in Marine Science, 2021)
Hyper-spectral and multi-spectral light sensors were used to examine the effects of elevated suspended sediment concentration (SSC) on the quantity and quality (spectral changes) of underwater downwelling irradiance in the turbid-zone coral reef communities of the inner, central Great Barrier Reef (GBR). Under elevated SSCs the shorter blue wavelengths were preferentially attenuated which together with attenuation of longer red wavelengths by pure water shifted the peak in the underwater irradiance spectrum ~100 nm to the less photosynthetically useful green-yellow waveband (peaking at ~575 nm). The spectral changes were attributed to mineral and detrital content of the terrestrially-derived coastal sediments as opposed to chromophoric (coloured) dissolved organic matter (CDOM). A simple blue to green (B/G, λ455:555 nm) ratio was shown to be useful in detecting sediment (turbidity) related decreases in underwater light as opposed to those associated with clouds which acted as neutral density filters. From a series of vertical profiles through turbid water, a simple, multiple component empirical optical model was developed that could accurately predict the light reduction and associated spectral changes as a function of SSC and water depth for a turbid-zone coral reef community of the inner GBR. The relationship was used to assess the response of a light sensitive coral, Pocillopora verrucosa in a 28-d exposure laboratory-based exposure study to a daily light integral of 1 or 6 mol quanta m 2 . PAR with either a broad spectrum or a green-yellow shifted spectrum. Light reduction resulted in a loss of the algal symbionts (zooxanthellae) of the corals (bleaching) and significant reduction in growth and lipid content. The 6 mol quanta m 2 d −1 PAR treatment with a green-yellow spectrum also resulted in a reduction in the algal density, Chl a content per cm 2 , lipids and growth compared to the same PAR daily light integral under a broad spectrum. Turbid zone coral reef communities are naturally light limited and given the frequency of sediment resuspension events that occur, spectral shifts are a common and previously unrecognised circumstance. Dedicated underwater light monitoring programs and further assessment of the spectral shifts by suspended sediments are essential for contextualising and further understanding the risk of enhanced sediment run-off to the inshore turbid water communities.

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

Evidence-Based Guidelines for Drug Interaction Studies: Model-Informed Time Course of Intestinal and Hepatic CYP3A4 Inhibition by Clarithromycin - Asha J Kapetas; Ahmad Y Abuhelwa; Michael J Sorich; Ross A McKinnon; A David Rodrigues; Andrew Rowland; Ashley M Hopkins (The AAPS Journal, 2021)

Preliminary survey of pests and diseases of eucheumatoid seaweed farms in the Philippines - Joseph P. Faisan; Ma. Rovilla J. Luhan; Rema C. Sibonga; Jonalyn P. Mateo; Victor Marco Emmanuel N. Ferriols; Janina Brakel; Georgia M. Ward; Stuart Ross; David Bass; Grant D. Stentiford; Juliet Brodie; Anicia Q. Hurtado (Journal of Applied Phycology, 2021)

Detection of genome edits in plants—from editing to seed - Raymond D. Shillito; Sherry Whitt; Margit Ross; Farhad Ghavami; David De Vleesschauwer; Katelijn D’Halluin; Annelies Van Hoecke; Frank Meulewaeter (In Vitro Cellular & Developmental Biology - Plant, 2021)
Genome editing (also known as gene editing) employs a range of tools such as Meganucleases, Zinc Finger Nucleases, TALENs, and more recently CRISPR to make defined changes in genes, regulatory sequences, untranslated regions, or intergenic regions. It is increasingly being applied in plant science research and to improve plant varieties. The benefits of having effective detection tools begin with optimization of the genome editing process itself and continue with selection and characterization of tissue cultures and/or regenerated plants. Detection tools are also used throughout the breeding process, and for preparation of regulatory dossiers when required, as well as for seed production, and may be necessary for monitoring products in the marketplace. Detection and identification of genome edits employs a wide range of analytical approaches including PCR, digital PCR, and sequencing methods. This article examines the applicability of each category of detection or identification approach, from the optimization of genome editing processes, through creation of edits, selection and characterization, and breeding. The challenges surrounding the detection of genome edits present at low levels in large seed, plant, or grain populations and of differentiating directed genome edits from conventional mutations are also explained.

The ecological impacts of multiple environmental stressors on coastal biofilm bacteria - Robert M. W. Ferguson; Eoin J. O’Gorman; David J. McElroy; Boyd A. McKew; Ross A. Coleman; Mark C. Emmerson; Alex J. Dumbrell (Global Change Biology, 2021)
Ecological communities are increasingly exposed to multiple interacting stressors. For example, warming directly affects the physiology of organisms, eutrophication stimulates the base of the food web, and harvesting larger organisms for human consumption dampens top‐down control. These stressors often combine in the natural environment with unpredictable results. Bacterial communities in coastal ecosystems underpin marine food webs and provide many important ecosystem services (e.g. nutrient cycling and carbon fixation). Yet, how microbial communities will respond to a changing climate remains uncertain. Thus, we used marine mesocosms to examine the impacts of warming, nutrient enrichment, and altered top‐predator population size structure (common shore crab) on coastal microbial biofilm communities in a crossed experimental design. Warming increased bacterial α‐diversity (18% increase in species richness and 67% increase in evenness), but this was countered by a decrease in α‐diversity with nutrient enrichment (14% and 21% decrease for species richness and evenness, respectively). Thus, we show some effects of these stressors could cancel each other out under climate change scenarios. Warming and top‐predator population size structure both affected bacterial biofilm community composition, with warming increasing the abundance of bacteria capable of increased mineralization of dissolved and particulate organic matter, such as Flavobacteriia, Sphingobacteriia, and Cytophagia. However, the community shifts observed with warming depended on top‐predator population size structure, with Sphingobacteriia increasing with smaller crabs and Cytophagia increasing with larger crabs. These changes could alter the balance between mineralization and carbon sequestration in coastal ecosystems, leading to a positive feedback loop between warming and CO 2 production. Our results highlight the potential for warming to disrupt microbial communities and biogeochemical cycling in coastal ecosystems, and the importance of studying these effects in combination with other environmental stressors.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

North Atlantic Basin-Scale Multi-Criteria Assessment Database to Inform Effective Management and Protection of Vulnerable Marine Ecosystems - Telmo Morato; Christopher K. Pham; Laurence Fauconnet; Gerald H. Taranto; Giovanni Chimienti; Erik Cordes; Carlos Dominguez-Carrió; Pablo Durán Muñoz; Hronn Egilsdottir; José-Manuel González-Irusta; Anthony Grehan; Dierk Hebbeln; et al. (Frontiers in Marine Science, 2021)

Climate sensitivity of understory trees differs from overstory trees in temperate mesic forests - Christine R. Rollinson; M. Ross Alexander; Alex W. Dye; David J. P. Moore; Neil Pederson; Valerie Trouet (Ecology, 2021)
The response of understory trees to climate variability is key to understanding current and future forest dynamics. However, analyses of climatic effects on tree growth have primarily focused on the upper canopy, leaving understory dynamics unresolved. We analyzed differences in climate sensitivity based on canopy position of four common tree species ( Acer rubrum , Fagus grandifolia , Quercus rubra , and Tsuga canadensis ) using growth information from 1,084 trees across eight sites in the northeastern United States. Effects of canopy position on climate response varied, but were significant and often nonlinear, for all four species. Compared to overstory trees, understory trees showed stronger reductions in growth at high temperatures and varied shifts in precipitation response. This contradicts the prevailing assumption that climate responses, particularly to temperature, of understory trees are buffered by the overstory. Forest growth trajectories are uncertain in compositionally and structurally complex forests, and future demography and regeneration dynamics may be misinferred if not all canopy levels are represented in future forecasts.

Teneurin C-Terminal Associated Peptide (TCAP)-3 Increases Metabolic Activity in Zebrafish - Ross M. Reid; Andrea L. Reid; David A. Lovejoy; Peggy R. Biga (Frontiers in Marine Science, 2021)
Teneurin C-terminal associated peptides (TCAP), bioactive peptides located on the C-terminal end of teneurin proteins, have been shown to regulate stress axis functions due to the high conservation between TCAP and corticotropin releasing factor (CRF). Additionally, recent work demonstrated that TCAP can increase metabolism in rats via glucose metabolism. These metabolic actions are not well described in other organisms, including teleosts. Here we investigated the expression of a tcap isoform, tcap-3 , and the potential role of TCAP-3 as a regulator of metabolism across zebrafish life-stages. Using pcr-based analyses, tcap-3 appears to be independently transcribed, in relation to teneurin-3 , in muscle tissue of adult zebrafish. Resazurin, respirometry chambers, and mitochondrial metabolism analyses were used to study the metabolic effects of synthetic rainbow trout TCAP-3 (rtTCAP-3) in larval and adult zebrafish. Overall, metabolic activity was enhanced by 48 h of rtTCAP-3 treatment in larvae (bath immersion) and adults (intraperitoneal injections). This metabolic activity increase was due to mitochondrial uncoupling, as mitochondrial respiration increase by rtTCAP-3 was due to proton leak. Additionally, rtTCAP-3 protected larval fish from reduced metabolic activity induced by low temperatures. Subsequently, rtTCAP-3 increased metabolic output in adult zebrafish subjected to accelerated swimming speeds, demonstrating the potent role of rtTCAP-3 in zebrafish metabolism regulation during metabolic challenges. Collectively, these results demonstrate the conserved roles for rtTCAP-3 as a metabolic activator in zebrafish.

First in class (S,E)-11-[2-(arylmethylene)hydrazono]-PBD analogs as selective CB2 modulators targeting neurodegenerative disorders - David Mingle; Meirambek Ospanov; Mohamed O. Radwan; Nicole Ashpole; Masami Otsuka; Samir A. Ross; Larry A. Walker; Abbas G. Shilabin; Mohamed A. Ibrahim (Medicinal Chemistry Research, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Invasion costs, impacts, and human agency: response to Sagoff 2020 - Ross N. Cuthbert; Sven Bacher; Tim M. Blackburn; Elizabeta Briski; Christophe Diagne; Jaimie T. A. Dick; Franz Essl; Piero Genovesi; Phillip J. Haubrock; Guillaume Latombe; Bernd Lenzner; Yves Meinard; et al. (Conservation Biology, 2020)
Article impact statement : In an era of profound biodiversity crisis, invasion costs, invader impacts, and human agency should not be dismissed.

Identification and Utilization of Biomarkers to Predict Response to Immune Checkpoint Inhibitors - Ole Gjoerup; Charlotte A. Brown; Jeffrey S. Ross; Richard S. P. Huang; Alexa Schrock; James Creeden; David Fabrizio; Khaled Tolba (The AAPS Journal, 2020)

Biological invasions in World Heritage Sites: current status and a proposed monitoring and reporting framework - Ross T. Shackleton; Bastian Bertzky; Louisa E. Wood; Nancy Bunbury; Heinke Jäger; Remco van Merm; Christian Sevilla; Kevin Smith; John R. U. Wilson; Arne B. R. Witt; David M. Richardson (Biodiversity and Conservation, 2020)
UNESCO World Heritage Sites (WHS) are areas of outstanding universal value and conservation importance. They are, however, threatened by a variety of global change drivers, including biological invasions. We assessed the current status of biological invasions and their management in 241 natural and mixed WHS globally by reviewing documents collated by UNESCO and IUCN. We found that reports on the status of biological invasions in WHS were often irregular or inconsistent. Therefore, while some reports were very informative, they were hard to compare because no systematic method of reporting was followed. Our review revealed that almost 300 different invasive alien species (IAS) were considered as a threat to just over half of all WHS. Information on IAS management undertaken in WHS was available for fewer than half of the sites that listed IAS as a threat. There is clearly a need for an improved monitoring and reporting system for biological invasions in WHS and likely the same for other protected areas globally. To address this issue, we developed a new framework to guide monitoring and reporting of IAS in protected areas building on globally accepted standards for IAS assessments, and tested it on seven WHS. The framework requires the collation of information and reporting on pathways, alien species presence, impacts, and management, the estimation of future threats and management needs, assessments of knowledge and gaps, and, using all of this information allows for an overall threat score to be assigned to the protected area. This new framework should help to improve monitoring of IAS in protected areas moving forward.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Creating positive synergies between risk management and transfer to accelerate food system climate resilience - Shahbaz Mushtaq; Jarrod Kath; Roger Stone; Ross Henry; Peter Läderach; Kathryn Reardon-Smith; David Cobon; Torben Marcussen; Neil Cliffe; Paul Kristiansen; Frederik Pischke (Climatic Change, 2020)

Temperature Dependence of High Frequency Irreversible Electroporation Evaluated in a 3D Tumor Model - Christopher C. Fesmire; Ross A. Petrella; Callie A. Fogle; David A. Gerber; Lei Xing; Michael B. Sano (Annals of Biomedical Engineering, 2020)

What lies beneath? Population dynamics conceal pace‐of‐life and sex ratio variation, with implications for resilience to environmental change - Julius G. Bright Ross; Chris Newman; Christina D. Buesching; David W. Macdonald (Global Change Biology, 2020)
Life‐history and pace‐of‐life syndrome theory predict that populations are comprised of individuals exhibiting different reproductive schedules and associated behavioural and physiological traits, optimized to prevailing social and environmental factors. Changing weather and social conditions provide in situ cues altering this life‐history optimality; nevertheless, few studies have considered how tactical, sex‐specific plasticity over an individual's lifespan varies in wild populations and influences population resilience. We examined the drivers of individual life‐history schedules using 31 years of trapping data and 28 years of pedigree for the European badger ( Meles meles L.), a long‐lived, iteroparous, polygynandrous mammal that exhibits heterochrony in the timing of endocrinological puberty in male cubs. Our top model for the effects of environmental (social and weather) conditions during a badger's first year on pace‐of‐life explained F / α ) and lifetime reproductive success. Conversely, sex ratio (SR) and sex‐specific density explained 52.8% (males) and 91.0% (females) of variance in adult F / α ratios relative to the long‐term population median F / α . Weather primarily affected the sexes at different life‐history stages, with energy constraints limiting the onset of male reproduction but playing a large role in female strategic energy allocation, particularly in relation to ongoing mean temperature increases. Furthermore, the effects of social factors on age of first reproduction and year‐to‐year reproductive success covaried differently with sex, likely due to sex‐specific responses to potential mate availability. For females, low same‐sex densities favoured early primiparity; for males, instead, up to 10% of yearlings successfully mated at high same‐sex densities. We observed substantial SR dynamism relating to differential mortality of life‐history strategists within the population, and propose that shifting ratios of ‘fast’ and ‘slow’ life‐history strategists contribute substantially to population dynamics and resilience to changing conditions.

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Where the wild things are! Do urban green spaces with greater avian biodiversity promote more positive emotions in humans? - Ross W. F. Cameron; Paul Brindley; Meghann Mears; Kirsten McEwan; Fiona Ferguson; David Sheffield; Anna Jorgensen; Julie Riley; Jon Goodrick; Liz Ballard; Miles Richardson (Urban Ecosystems, 2020)
Urban green space can help mitigate the negative impacts of urban living and provide positive effects on citizens’ mood, health and well-being. Questions remain, however, as to whether all types of green space are equally beneficial, and if not, what landscape forms or key features optimise the desired benefits. For example, it has been cited that urban landscapes rich in wildlife (high biodiversity) may promote more positive emotions and enhance well-being. This research utilised a mobile phone App, employed to assess people’s emotions when they entered any one of 945 green spaces within the city of Sheffield, UK. Emotional responses were correlated to key traits of the individual green spaces, including levels of biodiversity the participant perceived around them. For a subsample of these green spaces, actual levels of biodiversity were assessed through avian and habitat surveys. Results demonstrated strong correlations between levels of avian biodiversity within a green space and human emotional response to that space. Respondents reported being happier in sites with greater avian biodiversity ( p < 0.01, r = 0.78) and a greater variety of habitats ( p < 0.02, r = 0.72). Relationships were strengthened when emotions were linked to perceptions of overall biodiversity ( p < 0.001, r = 0.89). So, when participants thought the site was wildlife rich, they reported more positive emotions, even when actual avian biodiversity levels were not necessarily enhanced. The data strengthens the arguments that nature enhances well-being through positive affect, and that increased ‘engagement with nature’ may help support human health within urban environments. The results have strong implications for city planning with respect to the design, management and use of city green spaces.

A citizen science approach to long‐term monitoring of humpback whales ( Megaptera novaeangliae ) off Sydney, Australia - Vanessa Pirotta; Wayne Reynolds; Geoffrey Ross; Ian Jonsen; Alana Grech; David Slip; Robert Harcourt (Marine Mammal Science, 2020)
The Cape Solander Whale Migration Study is a citizen science project that annually counts northward migrating humpback whales ( Megaptera novaeangliae ) off Cape Solander, Sydney, Australia. Dedicated observers have compiled a 20‐year data set (1997–2017) of shore‐based observations from Cape Solander's high vantage point. Using this long‐term data set collected by citizen scientists, we sought to estimate the humpback whale population trend as it continues to recover postexploitation. We estimated an exponential growth rate of 0.099 (95% CI = 0.079–0.119) using a generalized linear model, based on observer effort (number of observation days) and number of whales observed, equating to 10% per annum growth in sightings since 1997. We found that favorable weather conditions for spotting whales off Cape Solander consisted of winds Balaenoptera musculus ) and data deficient species such as killer whales ( Orcinus orca ) and false killer whales ( Pseudorca crassidens ). Citizen science‐based studies can provide a cost‐effective approach to monitoring wildlife over the time necessary to detect change in a population. Information obtained from citizen science projects like this may help inform policy makers responsible for State and Federal protection of cetaceans in Australian waters and beyond.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Factors affecting the occurrence and activity of clouded leopards, common leopards and leopard cats in the Himalayas - Özgün Emre Can; Bhupendra Prasad Yadav; Paul J. Johnson; Joanna Ross; Neil D’Cruze; David W. Macdonald (Biodiversity and Conservation, 2020)
Clouded leopards are one of the least known of larger felids and were believed to be extinct in Nepal until 1987. They are particularly interesting because their Asian range spans a diversity of habitats in the fastest disappearing forests in the world and encompasses a guild which differs in composition from place to place. As a part of a wider camera-trapping study of this guild, involving 2948 camera traps at 45 sites in nine countries, and paralleling a similar study of the Sunda clouded leopard including a further 1544 camera traps spanning 22 sites distributed across two countries, we deployed 84 pairs of camera traps for 107 days in 2014 and 2015 at Langtang National Park, Nepal between 1823 and 3824 m a.s.l. within a grid encompassing c. 120 km 2 . We documented the presence of clouded leopards for the first time at an altitude as high as 3498 m a.s.l. Naïve occupancy for clouded leopard was 8.6% (correcting for detection, 10.1%). Clouded leopards were least active in the middle of the day, and largely crepuscular and nocturnal, as were the common leopards and leopard cats. The peak of clouded leopard activity overlapped with that of musk deer. Prey species for both clouded leopard and common leopard were available across the elevation range studied although the availability of some prey species declined as elevation increased, whereas Himalayan serow, Himalayan goral, and musk deer showed no association with elevation. Before this study, there was no hard evidence that clouded leopards occurred above 2300 m a.s.l., having documented them at almost 4000 m a.s.l. in the Himalayas, we emphasise the importance of this extreme portion of the species’ range where climate is likely to change more rapidly and with greater consequences, than the global average. The discovery of clouded leopards in Langtang National Park considerably extends their known range, and raises the possibility that they occur from the Terai in southern Nepal up to the Nepal-Tibet (China) border in the north. Insofar as this study has extended the known extreme boundary of the clouded leopard’s geographic range to encompass Langtang National Park in the Nepali Himalayas.

Determining Coral Density Thresholds for Identifying Structurally Complex Vulnerable Marine Ecosystems in the Deep Sea - Ashley A. Rowden; Tabitha R. R. Pearman; David Anthony Bowden; Owen F. Anderson; Malcolm Ross Clark (Frontiers in Marine Science, 2020)

A Reconfigurable In Vitro Model for Studying the Blood–Brain Barrier - Monica L. Moya; Michael Triplett; Melinda Simon; Javier Alvarado; Ross Booth; Joanne Osburn; David Soscia; Fang Qian; Nicholas O. Fischer; Kristen Kulp; Elizabeth K. Wheeler (Annals of Biomedical Engineering, 2020)

Evaluating the Impact of Climate Change on Water Quality and Quantity in an Urban Watershed Using an Ensemble Approach - Nasrin Alamdari; David J. Sample; Andrew C. Ross; Zachary M. Easton (Estuaries and Coasts, 2020)

Post-operative colorectal cancer surveillance: preference for optical colonoscopy over computerized tomographic colonography - David S. Weinberg; Jeremy Mitnick; Eileen Keenan; Tianyu Li; Eric A. Ross (Cancer Causes & Control, 2019)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Rewilding in the Garden: are garden hybrid plants (cultivars) less resilient to the effects of hydrological extremes than their parent species? A case study with Primula - Emma Lewis; Gareth K. Phoenix; Paul Alexander; John David; Ross W. F. Cameron (Urban Ecosystems, 2019)

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems - Steven A. Kannenberg; Kimberly A. Novick; M. Ross Alexander; Justin T. Maxwell; David J. P. Moore; Richard P. Phillips; William R. L. Anderegg (Global Change Biology, 2019)
Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (c) dendrochronological sampling biases. In order to link legacy effects from tree rings to whole forests, we leveraged a rich dataset from a Midwestern US forest that was severely impacted by a drought in 2012. At this site, we compiled tree‐ring records, leaf‐level gas exchange, eddy flux measurements, dendrometer band data, and satellite remote sensing estimates of greenness and leaf area before, during, and after the 2012 drought. After accounting for the relative abundance of tree species in the stand, we estimate that legacy effects led to ~10% reductions in tree‐ring width increments in the year following the severe drought. Despite this stand‐scale reduction in radial growth, we found that leaf‐level photosynthesis, gross primary productivity (GPP), and vegetation greenness were not suppressed in the year following the 2012 drought. Neither temporal asynchrony between radial growth and carbon uptake nor sampling biases could explain our observations of legacy effects in tree rings but not in GPP. Instead, elevated leaf‐level photosynthesis co‐occurred with reduced leaf area in early 2013, indicating that resources may have been allocated away from radial growth in conjunction with postdrought upregulation of photosynthesis and repair of canopy damage. Collectively, our results indicate that tree‐ring legacy effects were not observed in other canopy processes, and that postdrought canopy allocation could be an important mechanism that decouples tree‐ring signals from GPP.

The endangered White's seahorse Hippocampus whitei chooses artificial over natural habitats - Michael Simpson; Rebecca L. Morris; David Harasti; Ross A. Coleman (Journal of Fish Biology, 2019)
To explore whether the endangered White's seahorse Hippocampus whitei would choose to inhabit artificial over natural habitats, 10 adult H. whitei individuals were put through a series of binary choice trials in aquaria, during which they were offered different paired combinations of natural (different types of macroalga and seagrass) and artificial habitat (panels of swimming‐net material). It was found that H. whitei displayed a significant choice for swimming‐net material over all other available natural habitats and chose habitats according to the following rankings: (a) Net; (b) Sargassum sp.; (c) Posidonia australis ; (d) Zostera muelleri. Hippocampus whitei ’s choice of swimming net material over natural habitat suggests that these artificial structures could be a useful conservation measure for seahorses in areas where natural habitat is becoming less favourable due to declines in abundance or quality.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

An acute dose of inorganic dietary nitrate does not improve high-intensity, intermittent exercise performance in temperate or hot and humid conditions - Kieran Smith; David J. Muggeridge; Chris Easton; Mark D. Ross (European Journal of Applied Physiology, 2019)

The genomic pool of standing structural variation outnumbers single nucleotide polymorphism by threefold in the marine teleost Chrysophrys auratus - Andrew Catanach; Ross Crowhurst; Cecilia Deng; Charles David; Louis Bernatchez; Maren Wellenreuther (Molecular Ecology, 2019)
Recent studies have highlighted an important role of structural variation (SV) in ecological and evolutionary processes, but few have studied nonmodel species in the wild. As part of our long‐term research programme on the nonmodel teleost fish Australasian snapper ( Chrysophrys auratus ), we aim to build one of the first catalogues of genomic variants (SNPs and indels, and deletions, duplications and inversions) in fishes and evaluate overlap of genomic variants with regions under putative selection (Tajima's D and π ), and coding sequences (genes). For this, we analysed six males and six females from three locations in New Zealand and generated a high‐resolution genomic variation catalogue. We characterized 20,385 SVs and found they intersected with almost a third of all annotated genes. Together with small indels, SVs account for three times more variation in the genome in terms of bases affected compared to SNPs. We found that a sizeable portion of detected SVs was in the upper and lower genomic regions of Tajima's D and π , indicating that some of these have an effect on the phenotype. Together, these results shed light on the often neglected genomic variation that is produced by SVs and highlights the need to go beyond the mere measure of SNPs when investigating evolutionary processes, such as species diversification and adaptation.

Genome Comparisons of Wild Isolates of Caulobacter crescentus Reveal Rates of Inversion and Horizontal Gene Transfer - Bert Ely; Kiesha Wilson; Keshawn Ross; Damyen Ingram; Tajah Lewter; Jasmine Herring; David Duncan; Anthea Aikins; Derrick Scott (Current Microbiology, 2019)

Similar neurocognitive outcomes after 48 weeks in HIV-1-infected participants randomized to continue tenofovir/emtricitabine + atazanavir/ritonavir or simplify to abacavir/lamivudine + atazanavir - Kevin Robertson; Paul Maruff; Lisa L. Ross; David Wohl; Catherine B Small; Howard Edelstein; Mark S. Shaefer (Journal of NeuroVirology, 2019)

Evaluating centralized technical assistance as an implementation strategy to improve cancer prevention and control - Sarah Moreland-Russell; Prajakta Adsul; Seif Nasir; Maria E. Fernandez; Timothy J. Walker; Heather M. Brandt; Robin C. Vanderpool; Meagan Pilar; Paula Cuccaro; Wynne E. Norton; Cynthia A. Vinson; David A. Chambers; et al. (Cancer Causes & Control, 2018)

A reproductive and developmental screening study of the fungal toxin ochratoxin A in Fischer rats - Genevieve S. Bondy; Laurie Coady; Nikia Ross; Don Caldwell; Anne Marie Gannon; Keri Kwong; Stephen Hayward; David E. Lefebvre; Virginia Liston; Jayadev Raju; Peter Pantazopoulos; Ivan Curran (Mycotoxin Research, 2018)

Novel disturbance interactions between fire and an emerging disease impact survival and growth of resprouting trees - Allison B. Simler; Margaret R. Metz; Kerri M. Frangioso; Ross K. Meentemeyer; David M. Rizzo (Ecology, 2018)
Human‐altered ecological disturbances may challenge system resilience and disrupt biological legacies maintaining ecosystem recovery. Yet, the extent to which novel regimes challenge these legacies varies. This may be partially explained by differences in the vulnerability of life history strategies to disturbance characteristics. In the fire‐prone, resprouter‐dominated coast redwood forests of California, the introduced disease sudden oak death (SOD) alters fuel profiles, fire behavior, and aboveground tree mortality; however, this system is dominated by resprouting trees that are well‐adapted to aboveground damage, and belowground survival of individuals may represent the principal biological legacy connecting pre‐ and post‐fire communities. Much of the research exploring altered disturbances and forest recovery has focused on legacies determined by seed dispersal and aboveground survival of adults. In this work, we use pre‐ and post‐fire data from a long‐term monitoring network to assess the impacts of novel disturbance interactions between wildfire and SOD on the belowground survival and vegetative reproduction of resprouters. We found that increasing accumulation of coarse woody surface fuels from SOD‐killed hosts decreased the likelihood of belowground survival for resprouting tanoak trees, but not for redwoods. Tanoaks' belowground survival was negatively related to substrate burn severity, which increased with the volume of surface fuels from hosts, suggesting heat damage as a possible mechanism influencing altered patterns of resprouter mortality. These impacts increased with decreasing tree size. By contrast, redwood and tanoak trees that survived both disturbances resprouted more vigorously, regardless of post‐fire infection by P. ramorum , and generated similar recruitment at the stand level. Our results demonstrate that disease–fire interactions can narrow recruitment filters for resprouters, which could impact long‐term population and demographic structure; yet, compounded disturbance may also reduce stand density and disease pressure, allowing competitive release of survivors. Resprouters displayed vulnerabilities to altered disturbance, but our research suggests that legacies maintained by resprouting may be more resilient to certain compounded disturbances, compared to seed‐obligate species, because of high rates of individual survival under increasingly severe events. These trends have important implications for conservation of declining tree species in SOD‐impacted forests, as well as predictions of human impacts in other disturbance‐prone systems where resprouters are present.

Geographical ecology of dry forest tree communities in the West Indies - Janet Franklin; Riley Andrade; Mark L. Daniels; Patrick Fairbairn; Maria C. Fandino; Thomas W. Gillespie; Grizelle González; Otto Gonzalez; Daniel Imbert; Valerie Kapos; Daniel L. Kelly; Humfredo Marcano‐Vega; et al. (Journal of Biogeography, 2018)
Aim Seasonally dry tropical forest ( SDTF ) of the Caribbean Islands (primarily West Indies) is floristically distinct from Neotropical SDTF in Central and South America. We evaluate whether tree species composition was associated with climatic gradients or geographical distance. Turnover (dissimilarity) in species composition of different islands or among more distant sites would suggest communities structured by speciation and dispersal limitations. A nested pattern would be consistent with a steep resource gradient. Correlation of species composition with climatic variation would suggest communities structured by broad‐scale environmental filtering. Location The West Indies (The Bahamas, Cuba, Hispaniola, Jamaica, Puerto Rico, US Virgin Islands, Guadeloupe, Martinique, St. Lucia), Providencia (Colombia), south Florida ( USA ) and Florida Keys ( USA ). Taxon Seed plants—woody taxa (primarily trees). Methods We compiled 572 plots from 23 surveys conducted between 1969 and 2016. Hierarchical clustering of species in plots, and indicator species analysis for the resulting groups of sites, identified geographical patterns of turnover in species composition. Nonparametric analysis of variance, applied to principal components of bioclimatic variables, determined the degree of covariation in climate with location. Nestedness versus turnover in species composition was evaluated using beta diversity partitioning. Generalized dissimilarity modelling partitioned the effect of climate versus geographical distance on species composition. Results Despite a set of commonly occurring species, SDTF tree community composition was distinct among islands and was characterized by spatial turnover on climatic gradients that covaried with geographical gradients. Greater Antillean islands were characterized by endemic indicator species. Northern subtropical areas supported distinct, rather than nested, SDTF communities in spite of low levels of endemism. Main conclusions The SDTF species composition was correlated with climatic variation. SDTF on large Greater Antillean islands (Hispaniola, Jamaica and Cuba) was characterized by endemic species, consistent with their geological history and the biogeography of plant lineages. These results suggest that both environmental filtering and speciation shape Caribbean SDTF tree communities.

Relative influences of multiple sources of uncertainty on cumulative and incremental tree-ring-derived aboveground biomass estimates - M. Ross Alexander; Christine R. Rollinson; Flurin Babst; Valerie Trouet; David J. P. Moore (Trees, 2018)

Effect of copper on multiple successional stages of a marine fouling assemblage - David J. McElroy; Dieter F. Hochuli; Martina A. Doblin; Richard J. Murphy; Robert J. Blackburn; Ross A. Coleman (Biofouling, 2017)

Transcriptomic profiling of adaptive responses to ocean acidification - Priscila Goncalves; David B. Jones; Emma L. Thompson; Laura M. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2017)
Some populations of marine organisms appear to have inherent tolerance or the capacity for acclimation to stressful environmental conditions, including those associated with climate change. Sydney rock oysters from the B2 breeding line exhibit resilience to ocean acidification ( OA ) at the physiological level. To understand the molecular basis of this physiological resilience, we analysed the gill transcriptome of B2 oysters that had been exposed to near‐future projected ocean pH over two consecutive generations. Our results suggest that the distinctive performance of B2 oysters in the face of OA is mediated by the selective expression of genes involved in multiple cellular processes. Subsequent high‐throughput qPCR revealed that some of these transcriptional changes are exclusive to B2 oysters and so may be associated with their resilience to OA . The intracellular processes mediated by the differentially abundant genes primarily involve control of the cell cycle and maintenance of cellular homeostasis. These changes may enable B2 oysters to prevent apoptosis resulting from oxidative damage or to alleviate the effects of apoptosis through regulation of the cell cycle. Comparative analysis of the OA conditioning effects across sequential generations supported the contention that B2 and wild‐type oysters have different trajectories of changing gene expression and responding to OA . Our findings reveal the broad set of molecular processes underlying transgenerational conditioning and potential resilience to OA in a marine calcifier. Identifying the mechanisms of stress resilience can uncover the intracellular basis for these organisms to survive and thrive in a rapidly changing ocean.

Trophic state indicators are a better predictor of Florida bass condition compared to temperature in Florida’s freshwater bodies - Ross Boucek; Christian Barrientos; Michael R. Bush; David A. Gandy; Kyle L. Wilson; Joy M. Young (Environmental Biology of Fishes, 2017)

Rapid divergence of animal personality and syndrome structure across an arid-aquatic habitat matrix - Nicholas P. Moran; Krystina D. Mossop; Ross M. Thompson; David G. Chapple; Bob B. M. Wong (Oecologia, 2017)

Growing Pains: a Simulation-Based Curriculum for Improving the Transition to Hematology/Oncology Fellowship - Kim A. Reiss; Deepa Rangachari; David Cosgrove; Breelyn Wilky; Ross Donehower (Journal of Cancer Education, 2017)

Decadal declines in avian herbivore reproduction: density‐dependent nutrition and phenological mismatch in the Arctic - Megan V. Ross; Ray T. Alisauskas; David C. Douglas; Dana K. Kellett (Ecology, 2017)
A full understanding of population dynamics depends not only on estimation of mechanistic contributions of recruitment and survival, but also knowledge about the ecological processes that drive each of these vital rates. The process of recruitment in particular may be protracted over several years, and can depend on numerous ecological complexities until sexually mature adulthood is attained. We addressed long‐term declines (23 breeding seasons, 1992–2014) in the per capita production of young by both Ross's Geese ( Chen rossii ) and Lesser Snow Geese ( Chen caerulescens caerulescens ) nesting at Karrak Lake in Canada's central Arctic. During this period, there was a contemporaneous increase from 0.4 to 1.1 million adults nesting at this colony. We evaluated whether (1) density‐dependent nutritional deficiencies of pre‐breeding females or (2) phenological mismatch between peak gosling hatch and peak forage quality, inferred from NDVI on the brood‐rearing areas, may have been behind decadal declines in the per capita production of goslings. We found that, in years when pre‐breeding females arrived to the nesting grounds with diminished nutrient reserves, the proportional composition of young during brood‐rearing was reduced for both species. Furthermore, increased mismatch between peak gosling hatch and peak forage quality contributed additively to further declines in gosling production, in addition to declines caused by delayed nesting with associated subsequent negative effects on clutch size and nest success. The degree of mismatch increased over the course of our study because of advanced vegetation phenology without a corresponding advance in Goose nesting phenology. Vegetation phenology was significantly earlier in years with warm surface air temperatures measured in spring (i.e., 25 May–30 June). We suggest that both increased phenological mismatch and reduced nutritional condition of arriving females were behind declines in population‐level recruitment, leading to the recent attenuation in population growth of Snow Geese.

Factors influencing the post-exercise hepcidin-25 response in elite athletes - Peter Peeling; Alannah K. A. McKay; David B. Pyne; Kym J. Guelfi; Rachel H. McCormick; Coby M. Laarakkers; Dorine W. Swinkels; Laura A. Garvican-Lewis; Megan L. R. Ross; Avish P. Sharma; Jill J. Leckey; Louise M. Burke (European Journal of Applied Physiology, 2017)

Ecological niche partitioning within a large predator guild in a nutrient‐limited estuary - Philip Matich; Jerald S. Ault; Ross E. Boucek; David R. Bryan; Kirk R. Gastrich; Christine L. Harvey; Michael R. Heithaus; Jeremy J. Kiszka; Valeria Paz; Jennifer S. Rehage; Adam E. Rosenblatt (Limnology and Oceanography, 2017)
Within oligotrophic ecosystems, resource limitations coupled with interspecific variation in morphology, physiology, and life history traits may lead to niche partitioning among species. How generalist predators partition resources and their mechanisms, however, remain unclear across many ecosystems. We quantified niche partitioning among upper trophic level coastal and estuarine species: American alligators ( Alligator mississippiensis ), bull sharks ( Carcharhinus leucas ), common bottlenose dolphins ( Tursiops truncatus ), common snook ( Centropomus undecimalis ), and Atlantic tarpon ( Megalops atlanticus ) in the Shark River Estuary of the Florida Coastal Everglades, USA using acoustic telemetry, stable isotope analysis, and visual surveys, combined with published diet and life history demographic information. Spatial and isotopic niche overlap occurred among most species, with variability in partitioning among interspecific interactions. However, seasonal variability in habitat use, movements patterns, and trophic interactions may promote coexistence within this resource‐limited estuary. Beyond guild‐level niche partitioning, predators within the Shark River Estuary also exhibit partitioning within species through individual specializations and divergent phenotypes, which may lead to intraspecific variability in niche overlap with other predators. Niche differentiation expressed across multiple organizational levels (i.e., populations and communities) coupled with behavioral plasticity among predators in oligotrophic ecosystems may promote high species diversity despite resource limitations, which may be important when species respond to natural and human‐driven environmental change.

Chromolaena odorata (Siam weed) in eastern Africa: distribution and socio-ecological impacts - Ross T. Shackleton; Arne B. R. Witt; Winnie Nunda; David M. Richardson (Biological Invasions, 2017)

Approaches to Landscape Scale Inference and Study Design - Ross B. Cunningham; David B. Lindenmayer (Current Landscape Ecology Reports, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Body size over the life-course and the risk of endometrial cancer: the California Teachers Study - Pamela L. Horn-Ross; Alison J. Canchola; Leslie Bernstein; Dennis Deapen; James V. Lacey; Eunjung Lee; David O. Nelson; Peggy Reynolds (Cancer Causes & Control, 2016)

Rapid transcriptional acclimation following transgenerational exposure of oysters to ocean acidification - Priscila Goncalves; Kelli Anderson; Emma L. Thompson; Aroon Melwani; Laura m. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2016)
Marine organisms need to adapt in order to cope with the adverse effects of ocean acidification and warming. Transgenerational exposure to CO 2 stress has been shown to enhance resilience to ocean acidification in offspring from a number of species. However, the molecular basis underlying such adaptive responses is currently unknown. Here, we compared the transcriptional profiles of two genetically distinct oyster breeding lines following transgenerational exposure to elevated CO 2 in order to explore the molecular basis of acclimation or adaptation to ocean acidification in these organisms. The expression of key target genes associated with antioxidant defence, metabolism and the cytoskeleton was assessed in oysters exposed to elevated CO 2 over three consecutive generations. This set of target genes was chosen specifically to test whether altered responsiveness of intracellular stress mechanisms contributes to the differential acclimation of oyster populations to climate stressors. Transgenerational exposure to elevated CO 2 resulted in changes to both basal and inducible expression of those key target genes (e.g. ec SOD , catalase and peroxiredoxin 6), particularly in oysters derived from the disease‐resistant, fast‐growing B2 line. Exposure to CO 2 stress over consecutive generations produced opposite and less evident effects on transcription in a second population that was derived from wild‐type (nonselected) oysters. The analysis of key target genes revealed that the acute responses of oysters to CO 2 stress appear to be affected by population‐specific genetic and/or phenotypic traits and by the CO 2 conditions to which their parents had been exposed. This supports the contention that the capacity for heritable change in response to ocean acidification varies between oyster breeding lines and is mediated by parental conditioning.

Wildfire and forest disease interaction lead to greater loss of soil nutrients and carbon - Richard C. Cobb; Ross K. Meentemeyer; David M. Rizzo (Oecologia, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Erratum to: Identifying prey items from New Zealand fur seal (Arctocephalus forsteri) faeces using massive parallel sequencing - Arsalan Emami-Khoyi; David A. Hartley; Adrian M. Paterson; Laura J. Boren; Robert H. Cruickshank; James G. Ross; Elaine C. Murphy; Terry-Ann Else (Conservation Genetics Resources, 2016)

Identifying prey items from New Zealand fur seal (Arctocephalus forsteri) faeces using massive parallel sequencing - Arsalan Emami-Khoyi; David A. Hartley; Adrian M. Paterson; Laura J. Boren; Robert H. Cruickshank; James G. Ross; Elaine C. Murphy; Terry-Ann Else (Conservation Genetics Resources, 2016)

Advances in understanding the influence of fire on the ecology and evolution of plants: a tribute to Peter J. Clarke - Michael J. Lawes; David A. Keith; Ross A. Bradstock (Plant Ecology, 2016)

Identification of meteorological predictors of Fusarium graminearum ascospore release using correlation and causality analyses - Ray F. David; Amir E. BozorgMagham; David G. Schmale; Shane D. Ross; Linsey C. Marr (European Journal of Plant Pathology, 2016)

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Effects of individual, community, and landscape drivers on the dynamics of a wildland forest epidemic - Sarah E. Haas; J. Hall Cushman; Whalen W. Dillon; Nathan E. Rank; David M. Rizzo; Ross K. Meentemeyer (Ecology, 2016)
The challenges posed by observing host–pathogen–environment interactions across large geographic extents and over meaningful time scales limit our ability to understand and manage wildland epidemics. We conducted a landscape‐scale, longitudinal study designed to analyze the dynamics of sudden oak death (an emerging forest disease caused by Phytophthora ramorum ) across hierarchical levels of ecological interactions, from individual hosts up to the community and across the broader landscape. From 2004 to 2011, we annually assessed disease status of 732 coast live oak, 271 black oak, and 122 canyon live oak trees in 202 plots across a 275‐km 2 landscape in central California. The number of infected oak stems steadily increased during the eight‐year study period. A survival analysis modeling framework was used to examine which level of ecological heterogeneity best predicted infection risk of susceptible oak species, considering variability at the level of individuals (species identity, stem size), the community (host density, inoculum load, and species richness), and the landscape (seasonal climate variability, habitat connectivity, and topographic gradients). After accounting for unobserved risk shared among oaks in the same plot, survival models incorporating heterogeneity across all three levels better predicted oak infection than did models focusing on only one level. We show that larger oak trees (especially coast live oak) were more susceptible, and that interannual variability in inoculum production by the highly infectious reservoir host, California bay laurel, more strongly influenced disease risk than simply the density of this important host. Concurrently, warmer and wetter rainy‐season conditions in consecutive years intensified infection risk, presumably by creating a longer period of inoculum build‐up and increased probability of pathogen spillover from bay laurel to oaks. Despite the presence of many alternate host species, we found evidence of pathogen dilution, where less competent hosts in species‐rich communities reduce pathogen transmission and overall risk of oak infection. These results identify key parameters driving the dynamics of emerging infectious disease in California woodlands, while demonstrating how multiple levels of ecological heterogeneity jointly determine epidemic trajectories in wildland settings.

PCB remediation in schools: a review - Kathleen W. Brown; Taeko Minegishi; Cynthia Campisano Cummiskey; Matt A. Fragala; Ross Hartman; David L. MacIntosh (Environmental Science and Pollution Research, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Resolving future fire management conflicts using multicriteria decision making - Don A. Driscoll; Michael Bode; Ross A. Bradstock; David A. Keith; Trent D. Penman; Owen F. Price (Conservation Biology, 2016)
Management strategies to reduce the risks to human life and property from wildfire commonly involve burning native vegetation. However, planned burning can conflict with other societal objectives such as human health and biodiversity conservation. These conflicts are likely to intensify as fire regimes change under future climates and as growing human populations encroach farther into fire‐prone ecosystems. Decisions about managing fire risks are therefore complex and warrant more sophisticated approaches than are typically used. We applied a multicriteria decision making approach (MCDA) with the potential to improve fire management outcomes to the case of a highly populated, biodiverse, and flammable wildland–urban interface. We considered the effects of 22 planned burning options on 8 objectives: house protection, maximizing water quality, minimizing carbon emissions and impacts on human health, and minimizing declines of 5 distinct species types. The MCDA identified a small number of management options (burning forest adjacent to houses) that performed well for most objectives, but not for one species type (arboreal mammal) or for water quality. Although MCDA made the conflict between objectives explicit, resolution of the problem depended on the weighting assigned to each objective. Additive weighting of criteria traded off the arboreal mammal and water quality objectives for other objectives. Multiplicative weighting identified scenarios that avoided poor outcomes for any objective, which is important for avoiding potentially irreversible biodiversity losses. To distinguish reliably among management options, future work should focus on reducing uncertainty in outcomes across a range of objectives. Considering management actions that have more predictable outcomes than landscape fuel management will be important. We found that, where data were adequate, an MCDA can support decision making in the complex and often conflicted area of fire management.

Size‐balanced community reorganization in response to nutrients and warming - David J. McElroy; Eoin J. O'Gorman; Florian D. Schneider; Hanne Hetjens; Prune Le Merrer; Ross A. Coleman; Mark Emmerson (Global Change Biology, 2015)
It is widely accepted that global warming will adversely affect ecological communities. As ecosystems are simultaneously exposed to other anthropogenic influences, it is important to address the effects of climate change in the context of many stressors. Nutrient enrichment might offset some of the energy demands that warming can exert on organisms by stimulating growth at the base of the food web. It is important to know whether indirect effects of warming will be as ecologically significant as direct physiological effects. Declining body size is increasingly viewed as a universal response to warming, with the potential to alter trophic interactions. To address these issues, we used an outdoor array of marine mesocosms to examine the impacts of warming, nutrient enrichment and altered top‐predator body size on a community comprised of the predator (shore crab Carcinus maenas ), various grazing detritivores (amphipods) and algal resources. Warming increased mortality rates of crabs, but had no effect on their moulting rates. Nutrient enrichment and warming had near diametrically opposed effects on the assemblage, confirming that the ecological effects of these two stressors can cancel each other out. This suggests that nutrient‐enriched systems might act as an energy refuge to populations of species under metabolic constraints due to warming. While there was a strong difference in assemblages between mesocosms containing crabs compared to mesocosms without crabs, decreasing crab size had no detectable effect on the amphipod or algal assemblages. This suggests that in allometrically balanced communities, the expected long‐term effect of warming (declining body size) is not of similar ecological consequence to the direct physiological effects of warming, at least not over the six week duration of the experiment described here. More research is needed to determine the long‐term effects of declining body size on the bioenergetic balance of natural communities.

Polyploid and aneuploid detection in apple using a single nucleotide polymorphism array - David Chagné; Chris Kirk; Claire Whitworth; Sylvia Erasmuson; Ross Bicknell; Daniel J. Sargent; Satish Kumar; Michela Troggio (Tree Genetics & Genomes, 2015)

Stakeholder perceptions and practices regarding Prosopis (mesquite) invasions and management in South Africa - Ross T. Shackleton; David C. Le Maitre; David M. Richardson (Ambio, 2015)

Climatic, vegetation and edaphic influences on the probability of fire across mediterranean woodlands of south‐eastern Australia - Rebecca K. Gibson; Ross A. Bradstock; Trent Penman; David A. Keith; Don A. Driscoll (Journal of Biogeography, 2015)
Aim We investigated how the probability of burning is influenced by the time since fire ( TSF ) and gradients of climate, soil and vegetation in the fire‐prone mediterranean‐climate mallee woodlands of south‐eastern Australia. This provided insight into the processes controlling contemporary fuel dynamics and fire regimes across biogeographical boundaries, and the consequent effects of climate change on potential shifts in boundaries between fuel systems and fire regimes, at a subcontinental scale. Location South‐eastern Australia. Methods A desktop‐based GIS was used to generate random sampling points across the study region to collect data on intersecting fire interval, rainfall, vegetation and soil type. We used a Bayesian framework to examine the effects of combinations of rainfall, vegetation and soil type on the hazard‐of‐burning and survival parameters of the Weibull distribution. These analyses identify the nature of environmental controls on the length of fire intervals and the age‐dependence of the hazard of burning. Results Higher rainfall was consistently associated with shorter fire intervals. Within a single level of rainfall, however, the interaction between soil and vegetation type influenced the length of fire intervals. Higher‐fertility sands were associated with shorter fire intervals in grass‐dominated communities, whereas lower‐fertility sands were associated with shorter fire intervals in shrub‐dominated communities. The hazard of burning remained largely independent of TSF across the region, only markedly increasing with TSF in shrub‐dominated communities at high rainfall. Main conclusions Rainfall had a dominant influence on fire frequency in the mediterranean‐climate mallee woodlands of south‐eastern Australia. Predicted changes in the spatial distribution and amount of rainfall therefore have the potential to drive changes in fire regimes, although the effects of soil fertility and rainfall on fire regimes do not align on a simple productivity gradient. Reduced soil fertility may favour plant traits that increase the rate of woody litter fuel accumulation and flammability, which may alter the overriding influence of rainfall gradients on fire regimes.

Inkjet printing of insulin microneedles for transdermal delivery - Steven Ross; Nicolaos Scoutaris; Dimitrios Lamprou; David Mallinson; Dennis Douroumis (Drug Delivery and Translational Research, 2015)

Antagomirs targeting microRNA-134 increase hippocampal pyramidal neuron spine volume in vivo and protect against pilocarpine-induced status epilepticus - Eva M. Jimenez-Mateos; Tobias Engel; Paula Merino-Serrais; Isabel Fernaud-Espinosa; Natalia Rodriguez-Alvarez; James Reynolds; Cristina R. Reschke; Ronan M. Conroy; Ross C. McKiernan; Javier deFelipe; David C. Henshall (Brain Structure and Function, 2015)

Bond length estimates for oxide crystals with a molecular power law expression - G. V. Gibbs; Nancy L. Ross; David F. Cox (Physics and Chemistry of Minerals, 2015)

Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism - Alexandra C. G. Thomson; Paul H. York; Timothy M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2015)

A participatory systems approach to understanding climate adaptation needs - Helen Ross; Sylvie Shaw; David Rissik; Neil Cliffe; Susie Chapman; Vanessa Hounsell; James Udy; Nghia Trong Trinh; Jess Schoeman (Climatic Change, 2015)
Emerging literature on climate adaptation suggests the need for effective ways of engaging or activating communities and supporting community roles, coupled with whole-of-system approaches to understanding climate change and adaptation needs. We have developed and evaluated a participatory approach to elicit community and stakeholder understanding of climate change adaptation needs, and connect diverse community members and local office bearers towards potential action. The approach was trialed in a series of connected social-ecological systems along a transect from a rural area to the coast and islands of ecologically sensitive Moreton Bay in Queensland, Australia. We conducted ‘climate roundtables’ in each of three areas along the transect, then a fourth roundtable reviewed and extended the results to the region as a whole. Influence diagrams produced through the process show how each climate variable forecast to affect this region (heat, storm, flood, sea-level rise, fire, drought) affects the natural environment, infrastructure, economic and social behaviour patterns, and psychosocial responses, and how sets of people, species and ecosystems are affected, and act, differentially. The participatory process proved effective as a way of building local empathy, a local knowledge base and empowering participants to join towards future climate adaptation action. Key principles are highlighted to assist in adapting the process for use elsewhere.

A tree-ring perspective on the terrestrial carbon cycle - Flurin Babst; M. Ross Alexander; Paul Szejner; Olivier Bouriaud; Stefan Klesse; John Roden; Philippe Ciais; Benjamin Poulter; David Frank; David J. P. Moore; Valerie Trouet (Oecologia, 2014)

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

A trematode parasite alters growth, feeding behavior, and demographic success of invasive rusty crayfish (Orconectes rusticus) - Lindsey W. Sargent; Ashley K. Baldridge; Maraliz Vega-Ross; Kevin M. Towle; David M. Lodge (Oecologia, 2014)

Selection of low-variance expressed Malus x domestica (apple) genes for use as quantitative PCR reference genes (housekeepers) - Judith Bowen; Hilary S. Ireland; Ross Crowhurst; Zhiwei Luo; Amy E. Watson; Toshi Foster; Nigel Gapper; Jim J. Giovanonni; James P. Mattheis; Chris Watkins; David Rudell; Jason W. Johnston; et al. (Tree Genetics & Genomes, 2014)

Links between deep‐sea respiration and community dynamics - Henry A. Ruhl; Brian J. Bett; Sarah J. M. Hughes; Claudia H. S. Alt; Elizabeth J. Ross; Richard S. Lampitt; Corinne A. Pebody; Kenneth L. Smith; David S. M. Billett (Ecology, 2014)
It has been challenging to establish the mechanisms that link ecosystem functioning to environmental and resource variation, as well as community structure, composition, and compensatory dynamics. A compelling hypothesis of compensatory dynamics, known as “zero‐sum” dynamics, is framed in terms of energy resource and demand units, where there is an inverse link between the number of individuals in a community and the mean individual metabolic rate. However, body size energy distributions that are nonuniform suggest a niche advantage at a particular size class, which suggests a limit to which metabolism can explain community structuring. Since 1989, the composition and structure of abyssal seafloor communities in the northeast Pacific and northeast Atlantic have varied interannually with links to climate and resource variation. Here, for the first time, class and mass‐specific individual respiration rates were examined along with resource supply and time series of density and biomass data of the dominant abyssal megafauna, echinoderms. Both sites had inverse relationships between density and mean individual metabolic rate. We found fourfold variation in echinoderm respiration over interannual timescales at both sites, which were linked to shifts in species composition and structure. In the northeastern Pacific, the respiration of mobile surface deposit feeding echinoderms was positively linked to climate‐driven particulate organic carbon fluxes with a temporal lag of about one year, respiring ∼1–6% of the annual particulate organic carbon flux.

AutoGate: automating analysis of flow cytometry data - Stephen Meehan; Guenther Walther; Wayne Moore; Darya Orlova; Connor Meehan; David Parks; Eliver Ghosn; Megan Philips; Erin Mitsunaga; Jeffrey Waters; Aaron Kantor; Ross Okamura; et al. (Immunologic Research, 2014)

The Next Direction for Primatology? A Commentary on Setchell (2013) - Lydia M. Hopper; David B. Morgan; Stephen R. Ross (International Journal of Primatology, 2014)

Perspectives of spatial scale in a wildland forest epidemic - Whalen W. Dillon; Sarah E. Haas; David M. Rizzo; Ross K. Meentemeyer (European Journal of Plant Pathology, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Changing dominance of key plant species across a Mediterranean climate region: implications for fuel types and future fire regimes - Rebecca K. Gibson; Ross A. Bradstock; Trent D. Penman; David A. Keith; Don A. Driscoll (Plant Ecology, 2014)

Elemental composition of natural populations of key microbial groups in A tlantic waters - Carolina Grob; Martin Ostrowski; Ross J. Holland; Mikal Heldal; Svein Norland; Egil S. Erichsen; Claudia Blindauer; Adrian P. Martin; Mikhail V. Zubkov; David J. Scanlan (Environmental Microbiology, 2013)
Summary Intracellular carbon ( C ), nitrogen ( N ) and phosphorus ( P ) content of marine phytoplankton and bacterioplankton can vary according to cell requirements or physiological acclimation to growth under nutrient limited conditions. Although such variation in macronutrient content is well known for cultured organisms, there is a dearth of data from natural populations that reside under a range of environmental conditions. Here, we compare C , N and P content of S ynechococcus , P rochlorococcus , low nucleic acid ( LNA ) content bacterioplankton and small plastidic protists inhabiting surface waters of the North and South subtropical gyres and the E quatorial R egion of the A tlantic O cean. While intracellular C : N ratios ranged between 3.5 and 6, i.e. below the R edfield ratio of 6.6, all the C : P and N : P ratios were up to 10 times higher than the corresponding R edfield ratio of 106 and 16, respectively, reaching and in some cases exceeding maximum values reported in the literature. Similar C : P or N : P ratios in areas with different concentrations of inorganic phosphorus suggests that this is not just a response to the prevailing environmental conditions but an indication of the extremely low P content of these oceanic microbes.

Identification and characterization of an unusual metallo-β-lactamase from Serratia proteamaculans - Peter Vella; Manfredi Miraula; Emer Phelan; Eleanor W. W. Leung; Fernanda Ely; David L. Ollis; Ross P. McGeary; Gerhard Schenk; Nataša Mitić (JBIC Journal of Biological Inorganic Chemistry, 2013)

Unexpected redwood mortality from synergies between wildfire and an emerging infectious disease - Margaret R. Metz; J. Morgan Varner; Kerri M. Frangioso; Ross K. Meentemeyer; David M. Rizzo (Ecology, 2013)
An under‐examined component of global change is the alteration of disturbance regimes due to warming climates, continued species invasions, and accelerated land‐use change. These drivers of global change are themselves novel ecosystem disturbances that may interact with historically occurring disturbances in complex ways. Here we use the natural experiment presented by wildfires in redwood forests impacted by an emerging infectious disease to demonstrate unexpected synergies of novel disturbance interactions. The dominant tree, coast redwood (fire resistant without negative disease impacts), experienced unexpected synergistic increases in mortality when fire and disease co‐occurred. The increased mortality risk, more than fourfold at the peak of the effect, was not predictable from impacts of either disturbance alone. Changes in fire behavior associated with changes to forest fuels that occurred through disease progression overwhelmed redwood's usual resilience to wildfire. Our results demonstrate the potential for interacting disturbances to initiate novel successional trajectories and compromise ecosystem resilience.

The in vitro pharmacological profile of TD-1211, a neutral opioid receptor antagonist - Pamela R. Tsuruda; Ross G. Vickery; Daniel D. Long; Scott R. Armstrong; David T. Beattie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

The in vivo pharmacodynamics of the novel opioid receptor antagonist, TD-1211, in models of opioid-induced gastrointestinal and CNS activity - Scott R. Armstrong; Christina B. Campbell; Carrie L. Richardson; Ross G. Vickery; Pamela R. Tsuruda; Daniel D. Long; Sharath S. Hegde; David T. Beattie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Fire regimes of A ustralia: a pyrogeographic model system - Brett P. Murphy; Ross A. Bradstock; Matthias M. Boer; John Carter; Geoffrey J. Cary; Mark A. Cochrane; Roderick J. Fensham; Jeremy Russell‐Smith; Grant J. Williamson; David M. J. S. Bowman (Journal of Biogeography, 2013)
Aim Comparative analyses of fire regimes at large geographical scales can potentially identify ecological and climatic controls of fire. Here we describe A ustralia's broad fire regimes, and explore interrelationships and trade‐offs between fire regime components. We postulate that fire regime patterns will be governed by trade‐offs between moisture, productivity, fire frequency and fire intensity. Location Australia. Methods We reclassified a vegetation map of A ustralia, defining classes based on typical fuel and fire types. Classes were intersected with a climate classification to derive a map of ‘fire regime niches’. Using expert elicitation and a literature search, we validated each niche and characterized typical and extreme fire intensities and return intervals. Satellite‐derived active fire detections were used to determine seasonal patterns of fire activity. Results Fire regime characteristics are closely related to the latitudinal gradient in summer monsoon activity. Frequent low‐intensity fires occur in the monsoonal north, and infrequent, high‐intensity fires in the temperate south, demonstrating a trade‐off between frequency and intensity: that is, very high‐intensity fires are only associated with very low‐frequency fire regimes in the high biomass eucalypt forests of southern A ustralia. While these forests occasionally experience extremely intense fires (> 50,000 kW m −1 ), such regimes are exceptional, with most of the continent dominated by grass fuels, typically burning with lower intensity ( −1 ). Main conclusions Australia's fire regimes exhibit a coherent pattern of frequent, grass‐fuelled fires in many differing vegetation types. While eucalypts are a quintessential A ustralian entity, their contribution as a dominant driver of high‐intensity fire regimes, via their litter and bark fuels, is restricted to the forests of the continent's southern and eastern extremities. Our analysis suggests that the foremost driver of fire regimes at the continental scale is not productivity, as postulated conceptually, but the latitudinal gradient in summer monsoon rainfall activity.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Small fluctuations in the recovery of fusaria across consecutive sampling intervals with unmanned aircraft 100 m above ground level - Binbin Lin; Amir Bozorgmagham; Shane D. Ross; David G. Schmale III (Aerobiologia, 2013)

An enzyme activity capable of endotransglycosylation of heteroxylan polysaccharides is present in plant primary cell walls - Sarah L. Johnston; Roneel Prakash; Nancy J. Chen; Monto H. Kumagai; Helen M. Turano; Janine M. Cooney; Ross G. Atkinson; Robert E. Paull; Roshan Cheetamun; Antony Bacic; David A. Brummell; Roswitha Schröder (Planta, 2013)

SNP markers trace familial linkages in a cloned population of Pinus taeda—prospects for genomic selection - Jaime Zapata-Valenzuela; Fikret Isik; Christian Maltecca; Jill Wegrzyn; David Neale; Steve McKeand; Ross Whetten (Tree Genetics & Genomes, 2012)

Temporal variation in sex allocation in the mealybug Planococcus citri: adaptation, constraint, or both? - Laura Ross; Minke B. W. Langenhof; Ido Pen; David M. Shuker (Evolutionary Ecology, 2012)

Sea anemones may thrive in a high CO 2 world - David J. Suggett; Jason M. Hall‐Spencer; Riccardo Rodolfo‐Metalpa; Toby G. Boatman; Ross Payton; D. Tye Pettay; Vivienne R. Johnson; Mark E. Warner; Tracy Lawson (Global Change Biology, 2012)
Increased seawater p CO 2 , and in turn ‘ocean acidification’ (OA), is predicted to profoundly impact marine ecosystem diversity and function this century. Much research has already focussed on calcifying reef‐forming corals (Class: Anthozoa) that appear particularly susceptible to OA via reduced net calcification. However, here we show that OA‐like conditions can simultaneously enhance the ecological success of non‐calcifying anthozoans, which not only play key ecological and biogeochemical roles in present day benthic ecosystems but also represent a model organism should calcifying anthozoans exist as less calcified (soft‐bodied) forms in future oceans. Increased growth (abundance and size) of the sea anemone ( Anemonia viridis ) population was observed along a natural CO 2 gradient at Vulcano, Italy. Both gross photosynthesis ( P G ) and respiration (R) increased with p CO 2 indicating that the increased growth was, at least in part, fuelled by bottom up (CO 2 stimulation) of metabolism. The increase of P G outweighed that of R and the genetic identity of the symbiotic microalgae ( Symbiodinium spp.) remained unchanged (type A19) suggesting proximity to the vent site relieved CO 2 limitation of the anemones' symbiotic microalgal population. Our observations of enhanced productivity with p CO 2 , which are consistent with previous reports for some calcifying corals, convey an increase in fitness that may enable non‐calcifying anthozoans to thrive in future environments, i.e. higher seawater p CO 2 . Understanding how CO 2 ‐enhanced productivity of non‐ (and less‐) calcifying anthozoans applies more widely to tropical ecosystems is a priority where such organisms can dominate benthic ecosystems, in particular following localized anthropogenic stress.

Rosaceae conserved orthologous set (RosCOS) markers as a tool to assess genome synteny between Malus and Fragaria - Jill M. Bushakra; Daniel J. Sargent; Antonio Cabrera; Ross Crowhurst; Elena Lopez Girona; Riccardo Velasco; V. Vaughan Symonds; Esther van der Knaap; Michela Troggio; Susan E. Gardiner; David Chagné (Tree Genetics & Genomes, 2012)

Microbial biodiversity in a Malaysian oil field and a systematic comparison with oil reservoirs worldwide - Dongmei Li; David J. Midgley; Jason P. Ross; Yalchin Oytam; Guy C. J. Abell; Herbert Volk; Wan Ata Wan Daud; Philip Hendry (Archives of Microbiology, 2012)

Detrimental effects of West to East transmeridian flight on jump performance - Dale W. Chapman; Nicola Bullock; Angus Ross; Doug Rosemond; David T. Martin (European Journal of Applied Physiology, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Habitat Use by Coastal Birds Inferred from Stable Carbon and Nitrogen Isotopes - Ross A. Brittain; Arndt Schimmelmann; David F. Parkhurst; Christopher B. Craft (Estuaries and Coasts, 2012)

Common Factors Drive Disease and Coarse Woody Debris Dynamics in Forests Impacted by Sudden Oak Death - Richard C. Cobb; Maggie N. Chan; Ross K. Meentemeyer; David M. Rizzo (Ecosystems, 2012)

Effects of oxygen and culture system on in vitro propagation and redifferentiation of osteoarthritic human articular chondrocytes - Karsten Schrobback; Travis Jacob Klein; Ross Crawford; Zee Upton; Jos Malda; David Ian Leavesley (Cell and Tissue Research, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Adult exposure influences offspring response to ocean acidification in oysters - Laura M. Parker; Pauline M. Ross; Wayne A. O'Connor; Larissa Borysko; David A. Raftos; Hans‐Otto Pörtner (Global Change Biology, 2012)
It is essential to predict the impact of elevated P co 2 on marine organisms and habitats to anticipate the severity and consequences of future ocean chemistry change. Despite the importance of carry‐over effects in the evolutionary history of marine organisms, few studies have considered links between life‐history stages when determining how marine organisms will respond to elevated P co 2 , and none have considered the link between adults and their offspring. Herein, we exposed adults of wild and selectively bred Sydney rock oysters, S accostrea glomerata to elevated P co 2 during reproductive conditioning and measured the development, growth and survival response of their larvae. We found that elevated P co 2 had a negative impact on larvae of S . glomerata causing a reduction in growth, rate of development and survival. Exposing adults to elevated P co 2 during reproductive conditioning, however, had positive carry‐over effects on larvae. Larvae spawned from adults exposed to elevated P co 2 were larger and developed faster, but displayed similar survival compared with larvae spawned from adults exposed to ambient P co 2 . Furthermore, selectively bred larvae of S . glomerata were more resilient to elevated P co 2 than wild larvae. Measurement of the standard metabolic rate ( SMR ) of adult S . glomerata showed that at ambient P co 2 , SMR is increased in selectively bred compared with wild oysters and is further increased during exposure to elevated P co 2 . This study suggests that sensitive marine organisms may have the capacity to acclimate or adapt to elevated P co 2 over the next century and a change in energy turnover indicated by SMR may be a key process involved.

Translational PK–PD modelling of molecular target modulation for the AMPA receptor positive allosteric modulator Org 26576 - Roberta Bursi; Gul Erdemli; Robert Campbell; Matthew M. Hutmacher; Thomas Kerbusch; David Spanswick; Ross Jeggo; Kari R. Nations; Peter Dogterom; Jacques Schipper; Mohammed Shahid (Psychopharmacology, 2011)

Mathematical modeling of thermomechanical erosion beneath Proterozoic komatiitic basaltic sinuous rilles in the Cape Smith Belt, New Québec, Canada - David A. Williams; Ross C. Kerr; C. Michael Lesher (Mineralium Deposita, 2011)

HMC-1 human mast cells synthesize neurotensin (NT) precursor, secrete bioactive NT-like peptide(s) and express NT receptor NTS1 - David E. Cochrane; Robert E. Carraway; Kimberly Harrington; Melissa Laudano; Stephen Rawlings; Ross S. Feldberg (Inflammation Research, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Successful Surgical Intervention for the Management of Endocarditis due to Multidrug Resistant Candida parapsilosis: Case Report and Literature Review - Jessica Kumar; Douglas Fish; Harold Burger; Barbara Weiser; Jeffrey S. Ross; David Jones; Karl Robstad; Xiaojiang Li; Vishnu Chaturvedi (Mycopathologia, 2011)

Creative Solution for Implementation of Experiential, Competency-Based Palliative Care Training for Internal Medicine Residents - Douglas D. Ross; Deborah W. Shpritz; Susan D. Wolfsthal; Ann B. Zimrin; Timothy J. Keay; Hong-Bin Fang; Carl A. Schuetz; Laura M. Stapleton; David E. Weissman (Journal of Cancer Education, 2011)

Sewage contamination of a densely populated coral ‘atoll’ (Bermuda) - Ross Jones; Rachel Parsons; Elaine Watkinson; David Kendell (Environmental Monitoring and Assessment, 2011)

Complex Pharmacokinetics of a Humanized Antibody Against Human Amyloid Beta Peptide, Anti-Abeta Ab2, in Nonclinical Species - Yulia Vugmeyster; Pam Szklut; David Wensel; John Ross; Xin Xu; Michel Awwad; Davinder Gill; Lioudmila Tchistiakov; Garvin Warner (Pharmaceutical Research, 2011)

Medication incidents reported to an online incident reporting system - Adel Alrwisan; Jennifer Ross; David Williams (European Journal of Clinical Pharmacology, 2011)

Temperature, age of mating and starvation determine the role of maternal effects on sex allocation in the mealybug Planococcus citri - Laura Ross; Elizabeth J. Dealey; Leo W. Beukeboom; David M. Shuker (Behavioral Ecology and Sociobiology, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Investigation of the Ovarian and Prostate Cancer Peptidome for Candidate Early Detection Markers Using a Novel Nanoparticle Biomarker Capture Technology - Claudia Fredolini; Francesco Meani; Alessandra Luchini; Weidong Zhou; Paul Russo; Mark Ross; Alexis Patanarut; Davide Tamburro; Guido Gambara; David Ornstein; Franco Odicino; Monica Ragnoli; et al. (The AAPS Journal, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Grass invasion causes rapid increases in ecosystem carbon and nitrogen storage in a semiarid shrubland - ELIZABETH M. WOLKOVICH; DAVID A. LIPSON; ROSS A. VIRGINIA; KATHRYN L. COTTINGHAM; DOUGLAS T. BOLGER (Global Change Biology, 2010)
Accurately predicting terrestrial carbon (C) and nitrogen (N) storage requires understanding how plant invasions alter cycling and storage. A common, highly successful type of plant invasion occurs when the invasive species is of a distinctly different functional type than the native dominant plant, such as shrub encroachment throughout the western United States and annual grass invasions in Mediterranean shrublands, as studied here. Such invasions can dramatically transform landscapes and have large potential to alter C and N cycling by influencing storage in multiple pools. We used a manipulation of non‐native annual grass litter within a shrub‐dominated habitat in southern California (coastal sage scrub, CSS) to study how grass invasion alters ecosystem C and N storage. We added, removed, or left unchanged grass litter in areas of high and low invasion, then followed soil and vegetation changes. Grass litter greatly increased C and N storage in soil, aboveground native and non‐native biomass. Aboveground litter storage increased due to the greater inputs and slower decomposition of grass litter relative to shrub litter; shading by grass litter further reduced decomposition of both non‐native and native litter, which may be due to reduced photodegradation. Soil C and N pools in areas of high litter increased ∼20% relative to low litter areas in the two years following manipulation and were generally sinks for C and N, while areas with low litter were sources. We synthesize our results into a C cycle of invaded and uninvaded areas of CSS and link changes in storage to increases in the soil fungi : bacteria ratio, increased plant inputs, and decreased litter loss. Overall, we show that grasses, especially through their litter, control important abiotic and biotic mechanisms governing C and N storage, with widespread implications for C sequestration and N storage in semiarid systems undergoing grass or shrub invasions.

Apparent competition in canopy trees determined by pathogen transmission rather than susceptibility - Richard C. Cobb; Ross K. Meentemeyer; David M. Rizzo (Ecology, 2010)
Epidemiological theory predicts that asymmetric transmission, susceptibility, and mortality within a community will drive pathogen and disease dynamics. These epidemiological asymmetries can result in apparent competition, where a highly infectious host reduces the abundance of less infectious or more susceptible members in a community via a shared pathogen. We show that the exotic pathogen Phytophthora ramorum and resulting disease, sudden oak death, cause apparent competition among canopy trees and that transmission differences among canopy trees drives patterns of disease severity in California coast redwood forests. P. ramorum ranges in its ability to infect, sporulate on, and cause mortality of infected hosts. A path analysis showed that the most prolific inoculum producer, California bay laurel ( Umbellularia californica ), had a greater impact on the mortality rate of tanoak ( Lithocarpus densiflorus ) than did other inoculum‐supporting species. In stands experiencing high tanoak mortality, lack of negative impacts by P. ramorum on bay laurel may increase bay laurel density and subsequently result in positive feedback on pathogen populations. This study demonstrates the degree to which invasive, generalist pathogens can cause rapid changes in forest canopy composition and that differences in transmission can be more important than susceptibility in driving patterns of apparent competition.

Containment basin water quality fluctuation and implications for crop health management - Chuanxue Hong; John D. Lea-Cox; David S. Ross; Gary W. Moorman; Patricia A. Richardson; Sita R. Ghimire; Ping Kong (Irrigation Science, 2009)

Fluorescence fluctuation spectroscopy: ushering in a new age of enlightenment for cellular dynamics - David M. Jameson; Justin A. Ross; Joseph P. Albanesi (Biophysical Reviews, 2009)

The impact of everolimus versus mycophenolate on blood and lymphocyte cyclosporine exposure in heart-transplant recipients - Finn Gustafsson; David Barth; Diego H. Delgado; Meerna Nsouli; Jill Sheedy; Heather J. Ross (European Journal of Clinical Pharmacology, 2009)

The use of wetland water balances to link hydrogeological processes to ecological effects - David Gasca; Don Ross (Hydrogeology Journal, 2009)

Disturbance, rainfall and contrasting species responses mediated aboveground biomass response to 11 years of CO 2 enrichment in a Florida scrub‐oak ecosystem - TROY J. SEILER; DANIEL P. RASSE; JIAHONG LI; PAUL DIJKSTRA; HANS P. ANDERSON; DAVID P. JOHNSON; THOMAS L. POWELL; BRUCE A. HUNGATE; C. ROSS HINKLE; BERT G. DRAKE (Global Change Biology, 2009)
This study reports the aboveground biomass response of a fire‐regenerated Florida scrub‐oak ecosystem exposed to elevated CO 2 (1996–2007), from emergence after fire through canopy closure. Eleven years exposure to elevated CO 2 caused a 67% increase in aboveground shoot biomass. Growth stimulation was sustained throughout the experiment; although there was significant variability between years. The absolute stimulation of aboveground biomass generally declined over time, reflecting increasing environmental limitations to long‐term growth response. Extensive defoliation caused by hurricanes in September 2004 was followed by a strong increase in shoot density in 2005 that may have resulted from reopening the canopy and relocating nitrogen from leaves to the nutrient‐poor soil. Biomass response to elevated CO 2 was driven primarily by stimulation of growth of the dominant species, Quercus myrtifolia , while Quercus geminata , the other co‐dominant oak, displayed no significant CO 2 response. Aboveground growth also displayed interannual variation, which was correlated with total annual rainfall. The rainfall × CO 2 interaction was partially masked at the community level by species‐specific responses: elevated CO 2 had an ameliorating effect on Q. myrtifolia growth under water stress. The results of this long‐term study not only show that atmospheric CO 2 concentration had a consistent stimulating effect on aboveground biomass production, but also showed that available water is the primary driver of interannual variation in shoot growth and that the long‐term response to elevated CO 2 may have been caused by other factors such as nutrient limitation and disturbance.

Forest fine‐root production and nitrogen use under elevated CO 2 : contrasting responses in evergreen and deciduous trees explained by a common principle - OSKAR FRANKLIN; ROSS E. McMURTRIE; COLLEEN M. IVERSEN; KRISTINE Y. CROUS; ADRIEN C. FINZI; DAVID T. TISSUE; DAVID S. ELLSWORTH; RAM OREN; RICHARD J. NORBY (Global Change Biology, 2009)
Despite the importance of nitrogen (N) limitation of forest carbon (C) sequestration at rising atmospheric CO 2 concentration, the mechanisms responsible are not well understood. To elucidate the interactive effects of elevated CO 2 (eCO 2 ) and soil N availability on forest productivity and C allocation, we hypothesized that (1) trees maximize fitness by allocating N and C to maximize their net growth and (2) that N uptake is controlled by soil N availability and root exploration for soil N. We tested this model using data collected in Free‐Air CO 2 Enrichment sites dominated by evergreen ( Pinus taeda ; Duke Forest) and deciduous [ Liquidambar styraciflua ; Oak Ridge National Laboratory (ORNL)] trees. The model explained 80–95% of variation in productivity and N‐uptake data among eCO 2 , N fertilization and control treatments over 6 years. The model explains why fine‐root production increased, and why N uptake increased despite reduced soil N availability under eCO 2 at ORNL and Duke. In agreement with observations at other sites, the model predicts that soil N availability reduced below a critical level diminishes all eCO 2 responses. At Duke, a negative feedback between reduced soil N availability and N uptake prevented progressive reduction in soil N availability at eCO 2 . At ORNL, soil N availability progressively decreased because it did not trigger reductions in N uptake; N uptake was maintained at ORNL through a large increase in the production of fast turnover fine roots. This implies that species with fast root turnover could be more prone to progressive N limitation of carbon sequestration in woody biomass than species with slow root turnover, such as evergreens. However, longer term data are necessary for a thorough evaluation of this hypothesis. The success of the model suggests that the principle of maximization of net growth to control growth and allocation could serve as a basis for simplification and generalization of larger scale forest and ecosystem models, for example by removing the need to specify parameters for relative foliage/stem/root allocation.

Do we really need a central governor to explain brain regulation of exercise performance? A response to the letter of Dr. Marcora - Timothy David Noakes; Ross Tucker (European Journal of Applied Physiology, 2008)

Response of macroinvertebrate communities to remediation-simulating conditions in Pennsylvania streams influenced by acid mine drainage - Robert M. Ross; Eric S. Long; David S. Dropkin (Environmental Monitoring and Assessment, 2008)

Contaminant Concentrations and Histopathological Effects in Sacramento Splittail (Pogonichthys macrolepidotus) - Ben K. Greenfield; Swee J. Teh; John R. M. Ross; Jennifer Hunt; GuoHua Zhang; Jay A. Davis; Gary Ichikawa; David Crane; Silas S. O. Hung; DongFang Deng; Foo-Ching Teh; Peter G. Green (Archives of Environmental Contamination and Toxicology, 2008)

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Antibiotic and Disinfectant Susceptibility Profiles of Vancomycin-Resistant Enterococcus faecium (VRE) Isolated from Community Wastewater in Texas - Ross C. Beier; Sara E. Duke; Richard L. Ziprin; Roger B. Harvey; Michael E. Hume; Toni L. Poole; H. Morgan Scott; Linda D. Highfield; Walid Q. Alali; Kathleen Andrews; Robin C. Anderson; David J. Nisbet (Bulletin of Environmental Contamination and Toxicology, 2008)

The Highly Expressed and Inducible Endogenous NAD(P)H:quinone Oxidoreductase 1 in Cardiovascular Cells Acts as a Potential Superoxide Scavenger - Hong Zhu; Zhenquan Jia; James E. Mahaney; David Ross; Hara P. Misra; Michael A. Trush; Yunbo Li (Cardiovascular Toxicology, 2007)

Simulated mechanisms of soil N feedback on the forest CO 2 response - DAVID A. PEPPER; PETER E. ELIASSON; ROSS E. McMURTRIE; MARC CORBEELS; GÖRAN I. ÅGREN; MONIKA STRÖMGREN; SUNE LINDER (Global Change Biology, 2007)
An improved understanding of the response of forest ecosystems to elevated levels of CO 2 in the atmosphere is crucial because atmospheric CO 2 concentration continues to increase at an accelerating rate and forests are an important sink in the global carbon cycle. Several CO 2 ‐enrichment experiments have now been running for more than 10 years, with highly variable short‐term results after the first decade. Responses to rising [CO 2 ] over the next few decades will depend on several plant and ecosystem feedbacks that are inadequately understood. In this study, we conduct a sensitivity analysis, within the context of the simulated CO 2 response, using a new version of the G'DAY ecosystem model, with an improved decomposition submodel, applied to a nitrogen‐limited Norway spruce forest site in the north of Sweden. The new decomposition model incorporates important modifications to soil processes, including some that constitute negative feedbacks on an ecosystem's growth response to elevated [CO 2 ]. The sensitivity analysis reveals key parameters and processes that are important for the simulated CO 2 response on the short term and others that are more important on the long term. A process that has a strong impact on the short‐term response is a change in decomposer composition, potentially in response to altered litter quality. Parameters that become increasingly important in the long term are carbon allocation to root exudates that are directly or indirectly associated with atmospheric N 2 fixation, and the rate of humification of soil organic matter. We identify factors intrinsic to species and site (microbes and resources) and ecosystem nutrient supply that determine the duration of the enhanced simulated growth response to elevated [CO 2 ].

Identification of 54 large deletions/duplications in TSC1 and TSC2 using MLPA, and genotype-phenotype correlations - Piotr Kozlowski; Penelope Roberts; Sandra Dabora; David Franz; John Bissler; Hope Northrup; Kit Sing Au; Ross Lazarus; Dorota Domanska-Pakiela; Katarzyna Kotulska; Sergiusz Jozwiak; David J. Kwiatkowski (Human Genetics, 2007)

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; Megan K. Laird; Blake B. Ross; David H. Vaughan; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Surface Water Quality Impacts of Conservation Tillage Practices on Burley Tobacco Production Systems in Southwest Virginia - Brian L. Benham; David H. Vaughan; Megan K. Laird; Blake B. Ross; Danny R. Peek (Water, Air, & Soil Pollution, 2007)

Wine and other alcohol consumption and risk of ovarian cancer in the California Teachers Study cohort - Ellen T. Chang; Alison J. Canchola; Valerie S. Lee; Christina A. Clarke; David M. Purdie; Peggy Reynolds; Leslie Bernstein; Daniel O. Stram; Hoda Anton-Culver; Dennis Deapen; Harvey Mohrenweiser; David Peel; et al. (Cancer Causes & Control, 2007)

Rapid responses of vegetation to hydrological changes in Taylor Slough, Everglades National Park, Florida, USA - Thomas V. Armentano; Jay P. Sah; Michael S. Ross; David T. Jones; Hillary C. Cooley; Craig S. Smith (Hydrobiologia, 2006)

Interaction of hydrology and nutrient limitation in the Ridge and Slough landscape of the southern Everglades - Michael S. Ross; Sherry Mitchell-Bruker; Jay P. Sah; Stuart Stothoff; Pablo L. Ruiz; David L. Reed; Kris Jayachandran; Charles L. Coultas (Hydrobiologia, 2006)

Responses of twelve tree species common in Everglades tree islands to simulated hydrologic regimes - David T. Jones; Jay P. Sah; Michael S. Ross; Steven F. Oberbauer; Bernice Hwang; Krish Jayachandran (Wetlands, 2006)

Changes in soil carbon and nitrogen properties and microbial communities in relation to growth of Pinus radiata and Nothofagus fusca trees after 6 years at ambient and elevated atmospheric CO 2 - DES. J. ROSS; SUSAN J. GRAYSTON; DAVID WHITEHEAD (Global Change Biology, 2006)
Increasing atmospheric CO 2 concentration can influence the growth and chemical composition of many plant species, and thereby affect soil organic matter pools and nutrient fluxes. Here, we examine the effects of ambient (initially 362 μL L −1 ) and elevated (654 μL L −1 ) CO 2 in open‐top chambers on the growth after 6 years of two temperate evergreen forest species: an exotic, Pinus radiata D. Don, and a native, Nothofagus fusca (Hook. F.) Oerst. (red beech). We also examine associated effects on selected carbon (C) and nitrogen (N) properties in litter and mineral soil, and on microbial properties in rhizosphere and hyphosphere soil. The soil was a weakly developed sand that had a low initial C concentration of about 1.0 g kg −1 at both 0–100 and 100–300 mm depths; in the N. fusca system, it was initially overlaid with about 50 mm of forest floor litter (predominantly FH material) taken from a Nothofagus forest. A slow‐release fertilizer was added during the early stages of plant growth; subsequent foliage analyses indicated that N was not limiting. After 6 years, stem diameters, foliage N concentrations and C/N ratios of both species were indistinguishable ( P >0.10) in the two CO 2 treatments. Although total C contents in mineral soil at 0–100 mm depth had increased significantly ( P P. radiata , averaging 80±0.20 g m −2 yr −1 , they were not significantly influenced by elevated CO 2 . However, CO 2 ‐C production in litter, and CO 2 ‐C production, microbial C, and microbial C/N ratios in mineral soil (0–100 mm depth) under P. radiata were significantly higher under elevated than ambient CO 2 . CO 2 ‐C production, microbial C, and numbers of bacteria (but not fungi) were also significantly higher under elevated CO 2 in hyphosphere soil, but not in rhizosphere soil. Under N . fusca , some incorporation of the overlaid litter into the mineral soil had probably occurred; except for CO 2 ‐C production and microbial C in hyphosphere soil, none of the biochemical properties or microbial counts increased significantly under elevated CO 2 . Net mineral‐N production, and generally the potential utilization of different substrates by microbial communities, were not significantly influenced by elevated CO 2 under either tree species. Physiological profiles of the microbial communities did, however, differ significantly between rhizosphere and hyphosphere samples and between samples under P. radiata and N. fusca . Overall, results support the concept that a major effect on soil properties after prolonged exposure of trees to elevated CO 2 is an increase in the amounts, and mineralization rate, of labile organic components.

Early post-hurricane stand development in Fringe mangrove forests of contrasting productivity - Michael S. Ross; Pablo L. Ruiz; Jay P. Sah; David L. Reed; Joshua Walters; John F. Meeder (Plant Ecology, 2006)

Automated image processing method for the diagnosis and classification of malaria on thin blood smears - Nicholas E. Ross; Charles J. Pritchard; David M. Rubin; Adriano G. Dusé (Medical & Biological Engineering & Computing, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

Antibody-based therapeutics: Focus on prostate cancer - Jeffrey S. Ross; Karen E. Gray; Iain J. Webb; Gary S. Gray; Mark Rolfe; David P. Schenkein; David M. Nanus; Mathew I. Millowsky; Neil H. Bander (Cancer and Metastasis Reviews, 2005)

International Biofluid Mechanics Symposium: Position Papers and Key Challenges - Shmuel Einav; David Elad; C. Ross Ethier; Morteza Gharib (Annals of Biomedical Engineering, 2005)

How deep was the Dudley (UK) earthquake of 22 September 2002? - Ross Heyburn; David Bowers; Neil Selby; Alan Douglas (Journal of Seismology, 2005)

The response of heterotrophic CO 2 flux to soil warming - Peter E. Eliasson; Ross E. McMurtrie; David A. Pepper; Monika Strömgren; Sune Linder; Göran I. Ågren (Global Change Biology, 2005)
In a forest ecosystem at steady state, net carbon (C) assimilation by plants and C loss through soil and litter decomposition by heterotrophic organisms are balanced. However, a perturbation to the system, such as increased mean soil temperature, will lead to faster decay, enhancing CO 2 release from decomposers, and thus upsetting the balance. Recent in situ experiments have indicated that the stimulation of soil respiration following a step increase in annual average soil temperature declines over time. One possible explanation for this decline may be changes in substrate availability. This hypothesis is examined by using the ecosystem model G'DAY, which simulates C and nitrogen (N) dynamics in plants and soil. We applied the model to observations from a soil‐warming experiment in a Norway spruce ( Picea abies (L.) Karst.) stand by simulating a step increase of soil temperature. The model provided a good qualitative reproduction of the observed reduction of heterotrophic respiration ( R h ) under sustained warming. The simulations showed how the combined effects of faster turnover and reduced substrate availability lead to a transient increase of R h . The simulated annual increase in R h from soil was 60% in the first year after perturbation but decreased to 30% after a decade. One conclusion from the analysis of the simulations is that R h can decrease even though the temperature response function for decomposition remains unchanged. G'DAY suggests that acclimation of R h to soil warming is partly an effect of substrate depletion of labile C pools during the first decade of warming as a result of accelerated rates of mineralization. The response is attributed mainly to changing levels of C in pools with short time constants, reflecting the importance of high‐quality soil C fractions. Changes of the structure or physiology of the decomposer community were not invoked. Therefore, it becomes a question of definition whether the simulated dynamics of the declining response of CO 2 release to the warming should be named acclimation or seen as a natural part of the system dynamics.

The effect of additional virulence genes on transformation efficiency, transgene integration and expression in rice plants using the pGreen/pSoup dual binary vector system - Philippe Vain; Alison Harvey; Barbara Worland; Shona Ross; John W. Snape; David Lonsdale (Transgenic Research, 2004)

Long‐term carbon exchange in a sparse, seasonally dry tussock grassland - John E. Hunt; Francis M. Kelliher; Tony M. McSeveny; Des J. Ross; David Whitehead (Global Change Biology, 2004)
Rainfall and its seasonal distribution can alter carbon dioxide (CO 2 ) exchange and the sustainability of grassland ecosystems. Using eddy covariance, CO 2 exchange between the atmosphere and a sparse grassland was measured for 2 years at Twizel, New Zealand. The years had contrasting distributions of rain and falls (446 mm followed by 933 mm; long‐term mean=646 mm). The vegetation was sparse with total above‐ground biomass of only 1410 g m −2 . During the dry year, leaf area index peaked in spring (November) at 0.7, but it was The maximum daily net CO 2 uptake rate was only 1.5 g C m −2 day −1 , and it occurred before mid‐summer in both years. On an annual basis, for the dry year, 9 g C m −2 was lost to the atmosphere. During the wet year, 41 g C m −2 was sequestered from the atmosphere. The net exchange rates were determined mostly by the timing and intensity of spring rainfall. The components of ecosystem respiration were measured using chambers. Combining scaled‐up measurements with the eddy CO 2 effluxes, it was estimated that 85% of ecosystem respiration emanated from the soil surface. Under well‐watered conditions, 26% of the soil surface CO 2 efflux came from soil microbial activity. Rates of soil microbial CO 2 production and net mineral‐N production were low and indicative of substrate limitation. Soil respiration declined by a factor of four as the soil water content declined from field capacity (0.21 m 3 m −3 ) to the driest value obtained (0.04 m 3 m −3 ). Rainfall after periods of drought resulted in large, but short‐lived, respiration pulses that were curvilinearly related to the increase in root‐zone water content. Coupled with the low leaf area and high root : shoot ratio, this sparse grassland had a limited capacity to sequester and store carbon. Assuming a proportionality between carbon gain and rainfall during the summer, rainfall distribution statistics suggest that the ecosystem is sustainable in the long term.

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Effects of elevated atmospheric CO 2 on net ecosystem CO 2 exchange of a scrub–oak ecosystem - Graham J. Hymus; David P. Johnson; Sabina Dore; Hans P. Anderson; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2003)
We report the results of a 2‐year study of effects of the elevated (current ambient plus 350 μmol CO 2 mol −1 ) atmospheric CO 2 concentration ( C a ) on net ecosystem CO 2 exchange ( NEE ) of a scrub–oak ecosystem. The measurements were made in open‐top chambers (OTCs) modified to function as open gas‐exchange systems. The OTCs enclosed samples of the ecosystem (ca. 10 m 2 surface area) that had regenerated after a fire, 5 years before, in either current ambient or elevated C a . Throughout the study, elevated C a increased maximum NEE ( NEE max ) and the apparent quantum yield of the NEE ( φ NEE ) during the photoperiod. The magnitude of the stimulation of NEE max , expressed per unit ground area, was seasonal, rising from 50% in the winter to 180% in the summer. The key to this stimulation was effects of elevated C a , and their interaction with the seasonal changes in the environment, on ecosystem leaf area index, photosynthesis and respiration. The separation of these factors was difficult. When expressed per unit leaf area the stimulation of the NEE max ranged from 7% to 60%, with the increase being dependent on increasing soil water content ( W soil ). At night, the CO 2 effluxes from the ecosystem ( NEE night ) were on an average 39% higher in elevated C a . However, the increase varied between 6% and 64%, and had no clear seasonality. The partitioning of NEE night into its belowground ( R below ) and aboveground ( R above ) components was carried out in the winter only. A 35% and 27% stimulation of NEE night in December 1999 and 2000, respectively, was largely due to a 26% and 28% stimulation of R below in the respective periods, because R below constituted ca. 87% of NEE night . The 37% and 42% stimulation of R above in December 1999 and 2000, respectively, was less than the 65% and 80% stimulation of the aboveground biomass by elevated C a at these times. An increase in the relative amount of the aboveground biomass in woody tissue, combined with a decrease in the specific rate of stem respiration of the dominant species Quercus myrtifolia in elevated C a , was responsible for this effect. Throughout this study, elevated C a had a greater effect on carbon uptake than on carbon loss, in terms of both the absolute flux and relative stimulation. Consequently, for this scrub–oak ecosystem carbon sequestration was greater in the elevated C a during this 2‐year study period.

Cromakalim inhibits transmitter acetylcholine release in rat trachea by an action on epithelial cells and a diffusible factor - Ross Vlahos; Maurice E. Fabiani; David F. Story (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Effect of sampling strategy on measures of V?O2peak obtained using commercial breath-by-breath systems - David W. Hill; Lindsay P. Stephens; Sonja A. Blumoff-Ross; David C. Poole; Jimmy C. Smith (European Journal of Applied Physiology, 2003)

An arabinogalactan protein associated with secondary cell wall formation in differentiating xylem of loblolly pine - Yi Zhang; Garth Brown; Ross Whetten; Carol A. Loopstra; David Neale; Marcia J. Kieliszewski; Ronald R. Sederoff (Plant Molecular Biology, 2003)

Seasonal variation in the reproductive activity and biochemical composition of the Pacific oyster (Crassostrea gigas) from the Marlborough Sounds, New Zealand - Jeffrey S. Ren; Islay D. Marsden; Alex H. Ross; David R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2003)
Reproductive cycles of the Pacific oyster Crassostrea gigas (Thunberg) from the Marlborough Sounds, New Zealand, were followed between June 1998 and January 2000. Histological examination of the gonad confirms an annual cycle with a winter inactive period followed by rapid gonad development and a single short spawning period. The population gonad index correlated with seawater temperature and changes in tissue dry weight, condition index, and biochemical components. In winter, few individuals with early gametogenic stages were present and rapid development of primary oocytes (diam. 11 μm) occurred during spring (September‐November). The developmental rate and the diameter of mature oocytes (37 μm) was similar for the 1998 and 1999 seasons. For a standard 110‐mm‐length oyster, maximal tissue body weight and condition index were recorded in December. Rapid weight loss in January was length dependent and was attributed to spawning. Temperature was the environmental variable which best correlated with the timing of gametogenesis. Food availability (phytoplankton biomass) may have been responsible for inter‐annual variations. The biochemical composition (% glycogen, lipid, protein) of separated gonad and somatic tissues were variable seasonally and annually. Gametogenesis (oocyte diameter) was associated with increased gonad protein and glycogen and a decrease in lipid concentrations. These changes are similar to those in Pacific oyster populations from other parts of the world.

Development and Validation of a Herring Gull Embryo Toxicokinetic Model for PCBs - Ken G. Drouillard; Ross J. Norstrom; Glen A. Fox; Andy Gilman; David B. Peakall (Ecotoxicology, 2003)

The importance of alcohol-induced muscle disease - Victor R. Preedy; Kay Ohlendieck; Junko Adachi; Michael Koll; Alan Sneddon; Ross Hunter; Rajkumar Rajendram; David Mantle; Timothy J. Peters (Journal of Muscle Research and Cell Motility, 2003)

Using LCA to examine greenhouse gas abatement policy - Stuart Ross; David Evans; Michael Webber (The International Journal of Life Cycle Assessment, 2003)

High breast cancer incidence rates among California teachers: results from the California Teachers Study (United States) - Leslie Bernstein; Mark Allen; Hoda Anton-Culver; Dennis Deapen; Pamela L. Horn-Ross; David Peel; Richard Pinder; Peggy Reynolds; Jane Sullivan-Halley; Dee West; William Wright; Al Ziogas; et al. (Cancer Causes & Control, 2002)

A bovine whole-genome radiation hybrid panel and outline map - John L. Williams; André Eggen; Luca Ferretti; Christine J. Farr; Mathieu Gautier; Giuseppe Amati; Glynn Ball; Tiziana Caramorr; Ricky Critcher; Sandro Costa; Patrick Hextall; David Hills; et al. (Mammalian Genome, 2002)

Recent diet and breast cancer risk: the California Teachers Study (USA) - Pamela L. Horn-Ross; K.J. Hoggatt; Dee W. West; Melissa R. Krone; Susan L. Stewart; Hoda Anton-Culver; Leslie Bernstein; Dennis Deapen; David Peel; Richard Pinder; Peggy Reynolds; Ronald K. Ross; et al. (Cancer Causes & Control, 2002)

The use of life cycle assessment in environmental management - Stuart Ross; David Evans (The International Journal of Life Cycle Assessment, 2002)

Excluding site-specific data from the lca inventory: how this affects life cycle impact assessment - Stuart Ross; David Evans (The International Journal of Life Cycle Assessment, 2002)

Effects of dopamine D 4 receptor-selective antagonists on motor hyperactivity in rats with neonatal 6-hydroxydopamine lesions - Kehong Zhang; Eugen Davids; Frank Tarazi; Ross Baldessarini (Psychopharmacology, 2002)

Effects of resource quality on the population dynamics of the Indian meal moth Plodia interpunctella and its granulovirus - Ross I. McVean; Steve M. Sait; David J. Thompson; Mike Begon (Oecologia, 2002)

Stereoselective effects of methylphenidate on motor hyperactivity in juvenile rats induced by neonatal 6-hydroxydopamine lesioning - Eugen Davids; Kehong Zhang; Frank Tarazi; Ross Baldessarini (Psychopharmacology, 2002)

How LCA studies deal with uncertainty - Stuart Ross; David Evans; Michael Webber (The International Journal of Life Cycle Assessment, 2002)

Genetic, physical, and comparative map of the subtelomeric region of mouse Chromosome 4 - Xia Li; Alexander A. Bachmanov; Shanru Li; Zhenyu Chen; Michael G. Tordoff; Gary K. Beauchamp; Pieter J. de Jong; Chenyan Wu; Lianchun Chen; David B. West; David A. Ross; Jeffery D. Ohmen; et al. (Mammalian Genome, 2002)

Use of Life Cycle Assessment in Environmental Management - Stuart Ross; David Evans (Environmental Management, 2002)

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

A Parametric Approach to Measuring Cerebral Blood Flow Autoregulation from Spontaneous Variations in Blood Pressure - David M. Simpson; Ronney B. Panerai; David H. Evans; A. Ross Naylor (Annals of Biomedical Engineering, 2001)

Experimental Rock Outcrops Reveal Continuing Habitat Disturbance for an Endangered Australian Snake - Ross L. Goldingay; David A. Newell (Conservation Biology, 2000)

Experimental Rock Outcrops Reveal Continuing Habitat Disturbance for an Endangered Australian Snake - Ross L. Goldingay; David A. Newell (Conservation Biology, 2000)
Protected areas are commonly viewed as safe havens for endangered species. To test this notion, we experimentally constructed small rock outcrops for the endangered broad‐headed snake ( Hoplocephalus bungaroides ) within a national park near Sydney, Australia. Rock outcrops provide vital shelter sites during the cooler months of the year. Constructed rock outcrops (3 × 5 m) were placed at 11 paired sites located near (≤250 m) and far from (>400 m) walking tracks and roads. Eight of our 22 rock outcrops were disturbed by people over a 15‐month period. Disturbance consisted of displacement of some rocks or complete destruction of the outcrop. Disturbed outcrops occurred up to 450 m from a walking track or road. Disturbance to natural outcrops has also been observed in this park. This demonstrates a continuing decline in the quality of this snake's habitat. Twenty of our rock outcrops were colonized by velvet geckos ( Oedura lesueurii ), the primary prey of this snake. One broad‐headed snake was found in one outcrop. According to these findings, attempts to restore the habitat of this endangered snake should be centered on sites located ≥500 m from a walking track or road. Our study highlights the value of targeted experiments that precede larger‐scale habitat restoration.

Understanding the Tradeoffs Between Site Quality and Species Presence in Reserve Site Selection - Richard Church; Ross Gerrard; Allan Hollander; David Stoms (Forest Science, 2000)
A number of optimization models have been developed for natural reserve design and reserve site selection. The most common approach seeks to maximize the number of individual species that occur among chosen sites. A number of heuristics and mathematical programming algorithms have been applied to solve this problem. Although attaining maximum overall species representation is important, the relative quality of representation [which could be affected by site attributes such as habitat value, adequate population size, presence of critical resources, existence (or lack thereof) of exotic competitors, etc.] has been absent from most representation models. Yet issues of site quality should be considered in order to have any assurance of long-term species persistence in a reserve system. Here we present a multiobjective optimization model that addresses the issue of balancing species presence with habitat quality. One type of interesting alternative yields more high quality representation at the price of some reduction in overall representation. We present an application using a large dataset from California Gap Analysis to demonstrate this and other tradeoffs. Optimal solutions are attained using commercial integer programming software with very reasonable computational effort. For. Sci. 46(2):157-167.

Sustainable Forestry Oregon Style - Michael A. Bordelon; David C. McAllister; Ross Holloway (Journal of Forestry, 2000)
Over the past five years, the Oregon Department of Forestry has developed a new management plan for state forests in northwest Oregon. The approach results in health, productive, sustainable forest ecosystems and promotes the view that forest values such as timber and wildlife are compatible. Forest landscapes must be designed for wildlife habitat diversity, strategies must be operationally feasible, and the plan must be flexible enough to allow forest managers to address changes. Careful monitoring and an adaptive management approach are key to the plan's success over time.

A bovine YAC library containing four- to five-fold genome equivalents - David Hills; Simon Tracey; Julio Masabanda; Ruedi Fries; Leonard C. Schalkwyk; Hans Lehrach; J. Ross Miller; John L. Williams (Mammalian Genome, 1999)

An approach to modelling the impact of snow drift on glaciation in the Cairngorm Mountains, Scotland - Ross S. Purves; William A. Mackaness; David E. Sugden (Journal of Quaternary Science, 1999)

An approach to modelling the impact of snow drift on glaciation in the Cairngorm Mountains, Scotland - Ross S. Purves; William A. Mackaness; David E. Sugden (Journal of Quaternary Science, 1999)

Gene encoding polygalacturonase inhibitor in apple fruit is developmentally regulated and activated by wounding and fungal infection - Chenglin Yao; William S. Conway; Ruihua Ren; David Smith; Gavin S. Ross; Carl E. Sams (Plant Molecular Biology, 1999)

‘Candidatus Phytoplasma australiense’ is the phytoplasma associated with Australian grapevine yellows, papaya dieback and Phormium yellow leaf diseases - Lia W. Liefting; Anna C. Padovan; Karen S. Gibb; Ross E. Beever; Mark T. Andersen; Richard D. Newcomb; David L. Beck; Richard L.S. Forster (European Journal of Plant Pathology, 1998)

Roles for worms in reef-building - John M. Pandolfi; D. Ross Robertson; David W. Kirtley (Coral Reefs, 1998)

Mixture in the distribution of haloperidol-induced oral dyskinesias in the rat supports an animal model of tardive dyskinesia - Takeshi Hashimoto; David E. Ross; Xue-Min Gao; Deborah R. Medoff; C. A. Tamminga (Psychopharmacology, 1998)

Functional motifs in the IgH enhancer of the channel catfish - B. G. Magor; David A. Ross; Darlene L. Middleton; Gregory W. Warr (Immunogenetics, 1997)

The allopolyploid origin of kiwifruit,Actinidia deliciosa (Actinidiaceae) - Ross G. Atkinson; Guido Cipriani; David J. Whittaker; Richard C. Gardner (Plant Systematics and Evolution, 1997)

The Palmer LTER: A Long-Term Ecological Research Program at Palmer Station, Antarctica - Raymond Smith; Karen Baker; William Fraser; Eileen Hofmann; David Karl; John Klink; Langdon Quentin; Barbara Prezelin; Robin Ross; Wayne Trivelpiece; Maria Vernet (Oceanography, 1995)

U.S. Marine Scientific Research and Access to Foreign Waters - David Ross; Judith Fenwick (Oceanography, 1988)

Diploid male production ? a significant colony mortality factor in the fire ant Solenopsis invicta (Hymenoptera: Formicidae) - Kenneth G. Ross; David J. C. Fletcher (Behavioral Ecology and Sociobiology, 1986)

Comparative study of genetic and social structure in two forms of the fire ant Solenopsis invicta (Hymenoptera: Formicidae) - Keneth G. Ross; David J. C. Fletcher (Behavioral Ecology and Sociobiology, 1985)

Oscillatory neural networks in the rabbit hippocampus - David Ross; John M. Horowitz; Richard E. Plant (Biological Cybernetics, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Stimuli influencing mating behavior in the garter snake, Thamnophis radix - Patrick Ross; David Crews (Behavioral Ecology and Sociobiology, 1978)